Toner for electrostatic image development, electrostatic image developer, toner cartridge
By using toner for electrostatic image development with energy storage modulus and loss factor (tanδ) within a specific range, the image distortion problem caused by the offset of the recording medium during transmission is solved, and the image stability and image quality are improved. .
Patent Information
- Application Number
- CN202010151514.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-26
- Filing Date
- 2020-03-06
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2040-03-06
AI Technical Summary
In the image forming device, the recording medium may be offset during transmission, causing distortion of the recording medium, thereby causing fine fracture or deformation of the image, and reducing the image quality.
Provided is a toner for electrostatic image development, containing a bonding resin, and the energy storage modulus G'50T at 50°C is 2×106Pa or more, and the energy storage modulus at 100°C is 2×106Pa or more, and the energy storage modulus at 100°C is G'100T is 1×104Pa or more than 1×106Pa, and the tanδT in the entire temperature range of 50°C or more than 100°C or less is 0.05 or more than 1.5 or less.
This toner can suppress the occurrence of image roughness, improve the stability and image quality of the image, and prevent the negative impact of distortion of the recording medium on the image.
Smart Images

Figure BDA0002402598960000441 
Figure BDA0002402598960000451 
Figure BDA0002402598960000461
Abstract
Description
Technical Field
[0001] The present invention relates to a toner for developing an electrostatic image, an electrostatic image developer, and a toner cartridge. Background Art
[0002] In an image forming apparatus, a toner image formed on an image holder is transferred to a surface of a recording medium, and then the toner image is fixed to the recording medium by a fixing member that applies heat or pressure in contact with the toner image, thereby forming an image.
[0003] As a toner used in such an image forming device, for example, Japanese Patent Gazette No. 2002-182427 discloses "a toner for electrostatic image development, which is a toner for electrostatic image development containing particle aggregates formed by agglomeration of at least polymer primary particles and colorant primary particles, wherein the value of viscoelasticity tanδ of the toner in the temperature range of 100 to 200°C is in the range of 0.1 to 2."
[0004] In addition, Japanese Patent Application Laid-Open No. 2004-151438 discloses “a toner used in an image forming method having the following fixing step, wherein the fixing step comprises at least a heating metal sleeve having a flexible cylindrical metal tube as a base, a heating member arranged in contact with the inner surface of the heating metal sleeve and heating the heating metal sleeve, and a heating member having a heating member pressed against the heating member via the heating metal sleeve and having a heating member pressed against the heating metal sleeve. The fixing mechanism comprises a rotatable pressing member with a rotating shaft parallel to the sleeve, wherein a recording material formed with an unfixed toner image is passed through a fixing nip formed by pressing the above-mentioned heating metal sleeve and the above-mentioned pressing member, thereby fixing the above-mentioned unfixed toner image on the above-mentioned recording material, wherein the toner contains at least a binding resin, a colorant and a wax, and the maximum endothermic peak of the endothermic curve measured by a differential scanning calorimeter (DSC) is in the range of 60 to 135°C, and the loss modulus G" is 3×10 4 Pa temperature is 90 to 115 °C, and the loss modulus G" is shown to be 2×10 4 Pa temperature is 95 to 120 °C, and the loss modulus G" is shown as 1×10 4 The temperature of Pa is 105 to 135°C".
[0005] In addition, International Publication No. 2006 / 035862 discloses "a toner, which is a toner for electrostatic image development containing at least a binder resin and a colorant, wherein the binder resin includes an amorphous resin and a crystalline resin, and in a DSC curve at the time of heating measured by a differential scanning calorimeter, the starting temperature of the starting point is in the range of 100 to 150°C, the starting temperature of the end point is in the range of 150 to 200°C, and there is an endothermic peak with a half-peak width of 10 to 40°C."
[0006] In addition, Japanese Patent Application Laid-Open No. 2017-146568 discloses “a toner comprising a binder resin and a release agent, wherein in a molecular weight distribution of a THF-soluble component of the toner measured by GPC, when any molecular weight M in the range of 300 to 5,000 is selected, the difference between the maximum and minimum values of the peak intensity in the range of the molecular weight M±300 (a relative value when the value of the maximum intensity in the range of molecular weights of 20,000 or less is plotted as 100 in a molecular weight distribution curve measured by GPC with the vertical axis being the intensity and the horizontal axis being the molecular weight) is 30 or less, and the peak (930 cm-1) derived from a bisphenol A ethylene oxide adduct (BPA-EO) of the toner determined by FTIR-ATR (total reflection absorption infrared spectroscopy) method is 100 or less. -1 ) and the peak derived from the above-mentioned adhesive resin (828cm -1 ) is in the range of 0.20 to 0.40, and the peak P995 (995 cm-1) derived from the bisphenol A propylene oxide adduct (BPA-PO) of the toner is absent. -1 )”.
[0007] In addition, Japanese Patent Application Laid-Open No. 2015-114364 discloses “a toner comprising toner matrix particles, wherein the toner matrix particles contain a polyester resin (A) insoluble in tetrahydrofuran (THF), the toner matrix particles have a crystalline resin (B) on the outermost surface, the tetrahydrofuran (THF) insoluble component of the toner has a glass transition temperature [Tg1st (THF insoluble component)] of not less than -50°C and not more than 20°C in the first heating of differential scanning calorimetry (DSC), and the storage modulus [G' (THF insoluble component)] of the THF insoluble component of the toner at not less than 40°C and not more than 120°C measured by a rheometer is 1.0×10 5 Pa above 3.0×10 7 Below Pa". Summary of the invention
[0008] Technical problem to be solved by the invention
[0009] In an image forming apparatus, when a recording medium is conveyed by conveying rollers, the conveying timing at both ends of the recording medium may be offset, which may cause the recording medium to twist. Due to the twisting of the recording medium, the image may be finely broken or finely deformed, resulting in rough images and reduced image quality.
[0010] The object of the present invention is to provide a toner for electrostatic image development having a storage modulus G' at 50°C. 50T Less than 2×10 6 or greater than 3×10 8 In the case of 100T Less than 1×10 4 or greater than 1×10 6 or tanδ at at least a portion of the temperature between 50°C and 100°C T Compared with the case where the ratio is less than 0.05 or greater than 1.5, the occurrence of image roughness can be suppressed.
[0011] Technical solutions for solving technical problems
[0012] According to a first aspect of the present invention, there is provided a toner for electrostatic image development, comprising at least a binder resin and having a storage modulus G′ at 50° C. in a dynamic viscoelasticity measurement. 50T 2×10 6 Pa above 3×10 8 Pa below, storage modulus G' at 100℃ 100T 1×10 4 Pa or above 1×10 6 Pa or less, and tanδ in the entire temperature range of 50°C to 100°C T It is greater than 0.05 and less than 1.5.
[0013] According to the second aspect of the present invention, the above-mentioned adhesive resin includes at least: a crystalline resin A; an amorphous resin B1; and an amorphous resin B2, wherein the tan δ of the amorphous resin B2 in the entire temperature range of 50° C. to 100° C. in the dynamic viscoelasticity measurement is B2 Less than 1, storage modulus G' in the entire temperature range of 50°C to 100°C 50-100B2 1×10 3 Pa or above 1×10 7 Pa or less, and the content of the tetrahydrofuran-insoluble component is 90 mass % or more and 100 mass % or less.
[0014] According to the third aspect of the present invention, the storage modulus G′ of the substance other than the amorphous resin B2 contained in the electrostatic image developing toner at 50° C. in a dynamic viscoelasticity measurement is 50R 3×10 6 Pa above 9×10 8 Pa or less, and the storage modulus G' at 100°C 100R 1×10 3 Pa or above 1×10 5 Below Pa.
[0015] According to a fourth aspect of the present invention, the crystalline resin A is a crystalline polyester resin, and the non-crystalline resin B1 is a non-crystalline polyester resin.
[0016] According to a fifth aspect of the present invention, there is provided an electrostatic image developer comprising the above-mentioned electrostatic image developing toner.
[0017] According to a sixth aspect of the present invention, there is provided a toner cartridge that is detachably mounted in an image forming apparatus and stores the above-mentioned toner for developing an electrostatic image.
[0018] Effects of the Invention
[0019] According to the first or fourth embodiment, there is provided a toner for electrostatic image development, having a storage modulus G' at 50°C. 50T Less than 2×10 6 or greater than 3×10 8 In the case of 100T Less than 1×10 4 or greater than 1×10 6 or tanδ at at least a portion of the temperature between 50°C and 100°C T Compared with the case where the ratio is less than 0.05 or greater than 1.5, the provided scheme can suppress the occurrence of image roughness.
[0020] According to the second embodiment, there is provided a toner for electrostatic image development, wherein the tan delta of the toner and the amorphous resin B2 is 0.0447 W / m2 over the entire temperature range of 50° C. to 100° C. B2 When the storage modulus G' is 1 or more, it is within the entire temperature range of 50°C to 100°C. 50-100B2 Less than 1×10 3 Pa or greater than 1×10 7 The provided scheme can suppress the occurrence of image roughness compared with the case where the content of the tetrahydrofuran-insoluble component is less than 90 mass %.
[0021] According to the third embodiment, there is provided a toner for electrostatic image development, wherein the storage modulus G′ of the toner other than the non-crystalline resin B2 at 50° C. in a dynamic viscoelasticity measurement is 50R Less than 3×10 6 Pa or greater than 9×10 8 Pa, or the storage modulus G' at 100°C 100R Less than 1×10 3 Pa is greater than 1×10 5 Compared with the case of Pa, the provided scheme can suppress the occurrence of image roughness.
[0022] According to the fifth or sixth embodiment, an electrostatic image developer and a toner cartridge are provided, and the storage modulus G' at 50°C is used. 50T Less than 2×10 6 or greater than 3×10 8 The storage modulus G' of the electrostatic image developing toner at 100°C 100T Less than 1×10 4 or greater than 1×10 6 The electrostatic image developing toner, or the tan δ at at least a part of the temperature of 50°C to 100°C T Compared with the case where the electrostatic image developing toner has a relative humidity of less than 0.05 or more than 1.5, the provided scheme can suppress the occurrence of image roughness. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a cross-sectional image of an example of the toner according to the present embodiment.
[0024] Figure 2 This is a schematic structural diagram showing an example of the image forming apparatus according to the present embodiment.
[0025] Figure 3 This is a schematic structural diagram showing an example of the process cartridge according to the present embodiment. DETAILED DESCRIPTION
[0026] Hereinafter, embodiments of the present invention will be described.
[0027] <Toner for Electrostatic Image Development>
[0028] The electrostatic image developing toner (hereinafter also referred to as "toner") of the present embodiment contains at least a binder resin. In addition, the storage modulus G' of the toner at 50°C in the dynamic viscoelasticity measurement is 50T 2×10 6 Pa above 3×10 8 Pa below, storage modulus G' at 100℃ 100T1×10 4 Pa or above 1×10 6 Pa or less, and tanδ in the entire temperature range of 50°C to 100°C T It is greater than 0.05 and less than 1.5.
[0029] In an image forming device, a recording medium is conveyed from a recording medium storage unit to a toner image transfer mechanism and a fixing mechanism by a conveying roller. At this time, at both ends in a direction orthogonal to the recording medium conveying direction, an offset may occur at the moment of conveying, and in this case, the recording medium being conveyed may be twisted. It should be noted that, regarding such an offset, the simpler the function of the image forming device (for example, the lower the price of the image forming device), the more likely it is that the offset will occur. In addition, due to the distortion of the recording medium, the image may be finely broken or finely deformed, resulting in a rough image and reduced image quality.
[0030] It should be noted that, due to the use of thin recording media (e.g., basis weight 60 g / m 2 In the case of a paper (paper below 100 mm), distortion is more likely to occur, so the image roughness caused by the distortion of the recording medium is likely to become noticeable. In addition, in an image with a small printing area such as an image with only text, even if the recording medium is distorted, the effect on the image is small. On the other hand, in the case of an image with a large printing area (such as a solid image), the influence of the distortion of the recording medium on the image is greater, and the image roughness is also likely to become noticeable.
[0031] On the other hand, since the toner according to the present embodiment has the above-described configuration, even when the recording medium is twisted during transport, the occurrence of image roughness can be suppressed.
[0032] The reason is presumably as follows.
[0033] Storage modulus G' at 50℃ 50T Greater than 3×10 8 In the case of Pa, G' 50T If the toner is too hard, the image cannot follow the distortion of the recording medium, and the fixed image is prone to fine cracks, resulting in a rough image. 50T Less than 2×10 6 In the case of Pa, on the contrary, the toner is too soft, so that the fixed image is easily finely deformed, resulting in image roughness.
[0034] Storage modulus G' at 100℃ 100T Less than 1×10 4In the case of Pa, the toner excessively penetrates into the recording medium during fixing, and is very susceptible to the distortion of the recording medium, causing fine cracks in the image and image roughness. On the other hand, G' 100T Greater than 1×10 6 In the case of Pa, on the contrary, the toner does not penetrate into the recording medium too much during fixing, and the fixing strength of the image is reduced, so that the recording medium is easily broken due to twisting, resulting in image roughness.
[0035] It should be noted that, in addition to the above G' 50T and G' 100T In addition to the control of tanδ in the entire temperature range of 50℃ to 100℃, T By controlling the image roughness, the occurrence of image roughness can be suppressed. T It is the ratio of the loss modulus to the storage modulus of the toner in the entire temperature range of 50°C to 100°C. T When the value is greater than 1.5, the toner is dominated by viscosity, so the image strength is likely to decrease, and the image may be broken due to the distortion of the recording medium, resulting in image roughness. T When the molecular weight is less than 0.05, the toner is dominated by elasticity, and thus the adhesion to the recording medium is reduced, and the fixing strength is reduced. As a result, the recording medium is easily broken due to twisting, resulting in rough images.
[0036] In contrast, in this embodiment, by making the storage modulus G' at 50°C 50T , Storage modulus G' at 100℃ 100T And tanδ in the entire temperature range from 50℃ to 100℃ T When the content is within the above ranges, even when the recording medium is twisted during transport, the occurrence of fine cracks or fine deformations in the image can be suppressed, and as a result, image roughness can be suppressed.
[0037] Storage modulus G' of toner at 50℃ 50T
[0038] The storage modulus G′ of the toner of this embodiment at 50° C. in the dynamic viscoelasticity measurement is 50T 2×10 6 Pa above 3×10 8 Pa or less. It should be noted that, from the perspective of easily suppressing the occurrence of image roughness, G' 50T Preferably 6×10 6 Pa or above 1×10 8 Pa or less, more preferably 1×10 7 Pa or above 1×108 Below Pa.
[0039] Storage modulus G' of toner at 100℃ 100T
[0040] The storage modulus G′ of the toner of this embodiment at 100° C. in the dynamic viscoelasticity measurement is 100T 1×10 4 Above 1×10 6 It should be noted that, from the perspective of easily suppressing the occurrence of image roughness, G' 100T Preferably 1×10 4 Pa or above 1×10 5 Pa or less, more preferably 1×10 4 Pa above 5×10 4 Below Pa.
[0041] ·Tanδ of the toner in the entire temperature range of 50°C to 100°C T
[0042] The toner of the present embodiment has a tan δ value in the entire temperature range of 50° C. to 100° C. in dynamic viscoelasticity measurement. T It is greater than 0.05 and less than 1.5.
[0043] It should be noted that since the contamination of the fixing roller by the toner can be suppressed for a long time, tan δ T It is preferably 0.05 to 0.5, and more preferably 0.1 to 0.4.
[0044] On the other hand, from the perspective of maintaining stable image gloss regardless of temperature, tan δ T It is preferably 0.6 or more and less than 1.0, and more preferably 0.7 or more and 0.9 or less.
[0045] In addition, since the toner can maintain the releasability from the fixing roller after melting, and has high wettability and deformability to paper and moderate viscoelasticity, tanδ T It is preferably 1.0 to 1.5, and more preferably 1.1 to 1.3.
[0046] Here, the measurement of dynamic viscoelasticity of toner will be described.
[0047] About the loss tangent tanδ in the measurement of dynamic viscoelasticity of toner T(i.e., the mechanical loss tangent of dynamic viscoelasticity), the storage modulus G' and loss modulus G" are determined by measuring the temperature dependence of dynamic viscoelasticity, and are defined by G" / G'. Here, G' is the elastic response component of the elastic modulus in the relationship between stress and strain when deformation occurs, which stores the energy that does work on the deformation. The viscous response component of the elastic modulus is G". In addition, tanδ defined by G" / G' T It is a measure of the ratio of energy lost and stored for work done on deformation.
[0048] The dynamic viscoelasticity measurement was performed using a rheometer.
[0049] Specifically, the toner to be measured is formed into a tablet at room temperature (e.g., 25° C.) using a press molding machine to prepare a sample for measurement. The sample for measurement is then subjected to a dynamic viscoelasticity measurement using a rheometer under the following conditions, and the storage modulus G' at 50° C. is obtained from the obtained storage modulus and loss modulus curves. 50T , Storage modulus G' at 100℃ 100T And tanδ in the entire temperature range from 50℃ to 100℃ T .
[0050] -Measurement conditions-
[0051] Measuring device: Rheometer ARES (manufactured by TA Instruments)
[0052] Measuring fixture: 8mm parallel plate
[0053] Gap: adjusted to 4mm
[0054] Frequency: 1Hz
[0055] Measurement temperature: Measurement is carried out under the condition of increasing the temperature from 25°C to the maximum reaching temperature of 150°C Strain: 0.03~20% (automatic control)
[0056] Heating rate: 1℃ / min
[0057] It should be noted that the storage modulus G' of the toner 50T , storage modulus G' 100T and tanδ T The method of performing the control is not particularly limited.
[0058] For example, the storage modulus G' of the toner 50T and storage modulus G' 100TThe control method of the toner can include the storage modulus G' of the binder resin at 50°C and 100°C and the amount of the binder resin. In addition, when two or more binder resins are used, the content ratio of each binder resin and the storage modulus G' of each binder resin at 50°C and 100°C can be mentioned. In addition, when one or more of the two or more binder resins form a domain, the particle size of the domain can be mentioned.
[0059] In addition, as the tan δ of the toner T The control method includes the storage modulus G' and loss modulus G" of the binding resin in the toner in the entire temperature range of not less than 50°C and not more than 100°C, the amount of the binding resin, and the presence or absence of tetrahydrofuran (THF) insoluble components and their amount. In addition, when using two or more binding resins, the content ratio of each binding resin and the storage modulus G' and loss modulus G" of each binding resin in the entire temperature range of not less than 50°C and not more than 100°C can be mentioned. In addition, when one or more of the two or more binding resins and at least one of the THF insoluble components form a region, the particle size of the region can be mentioned.
[0060] It should be noted that the storage modulus G' of the toner is 50T , storage modulus G' 100T and tanδ T From the aspect of controlling within the above range, the toner of this embodiment preferably has a structure in which a discontinuous phase containing a binder resin is dispersed in a continuous phase containing a binder resin. That is, it is preferably a toner in which a continuous phase corresponding to a sea and a discontinuous phase corresponding to an island (domain) form a so-called sea island structure.
[0061] Here, as a toner having a sea-island structure, for example, toners having the following two structures can be mentioned.
[0062] (1) A toner having a structure having a continuous phase containing a binder resin (i) and a discontinuous phase having a core containing a binder resin (ii) and a coating layer covering the core and containing a binder resin (iii).
[0063] (2) A toner having a structure including a binder resin and a tetrahydrofuran (THF)-insoluble component, wherein the THF-insoluble component forms a discontinuous phase.
[0064] (1) Toner having a structure of a continuous phase and a discontinuous phase (the discontinuous phase having a core and a coating layer)
[0065] The toner having the above-mentioned structure (1) will be described by taking an example.
[0066] Figure 1 This is a cross-sectional image of an example of the toner according to this embodiment having the above-mentioned structure (1). Figure 1 The toner shown includes: a continuous phase 40 containing a binder resin (i); and a discontinuous phase 50 dispersed in the continuous phase 40, and the discontinuous phase 50 has: a core 52 containing a binder resin (ii), and a coating layer 54 covering the core 52 and containing a binder resin (iii). That is, the continuous phase 40 corresponding to the sea and the discontinuous phase 50 corresponding to the island (region) form a so-called sea island structure, and the discontinuous phase 50 corresponding to the island has a structure having a core 52 and a coating layer 54 surrounding it. It should be noted that Figure 1 The toner shown contains a release agent 60 .
[0067] -Binder resin contained in the continuous phase, the core and the coating layer-
[0068] The binder resin (i) contained in the continuous phase, the binder resin (ii) contained in the core portion, and the binder resin (iii) contained in the coating layer may be the same resin or different resins.
[0069] It should be noted that the “different resins” mentioned here include: resins having different structures as structural units in the polymer chain (for example, resins synthesized using monomers with different molecular structures as raw materials); resins having the same structure as structural units in the polymer chain but different average molecular weights; and the like.
[0070] ·Binder resin (i) contained in the continuous phase
[0071] The continuous phase preferably contains a crystalline resin and an amorphous resin as the binder resin (i). By containing a crystalline resin in the continuous phase, it is easy to improve the low-temperature fixability. It should be noted that from the perspective of improving the low-temperature fixability, it is more preferred that the continuous phase contains a crystalline polyester resin and an amorphous polyester resin. (It should be noted that, hereinafter, the crystalline polyester resin contained in the continuous phase is recorded as "a", and the amorphous polyester resin contained in the continuous phase is recorded as "b1".)
[0072] The mass ratio of the crystalline resin to the non-crystalline resin contained in the continuous phase (more preferably the mass ratio (a / b1) of the crystalline polyester resin a to the non-crystalline polyester resin b1) is preferably 0.04 to 1.0, more preferably 0.09 to 0.6, and further preferably 0.1 to 0.4.
[0073] By setting the mass ratio of the crystalline resin to the amorphous resin (more preferably the mass ratio of the crystalline polyester resin a to the amorphous polyester resin b1 (a / b1)) to 0.04 or more, it is easy to improve the low-temperature fixing property. On the other hand, by setting the mass ratio to 1.0 or less, it is easy to improve the image fixing strength.
[0074] It should be noted that the crystalline resin and the amorphous resin contained in the continuous phase may be one type or two or more types, respectively. Also, the crystalline polyester resin a and the amorphous polyester resin b1 contained in the continuous phase may be one type or two or more types, respectively.
[0075] The total content of the crystalline polyester resin a and the non-crystalline polyester resin b1 in the entire binder resin contained in the continuous phase is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 100% by mass.
[0076] Adhesive resin (ii) contained in the core
[0077] The core part preferably contains an amorphous resin (more preferably an amorphous polyester resin) as the binding resin (ii).
[0078] In addition, as described below, when the glass transition temperature Tg of the adhesive resin (iii) contained in the coating layer is lower than the fixing temperature, it is more preferable that the core contains an amorphous resin (more preferably an amorphous polyester resin). The amorphous resin in the core is dissolved from the discontinuous phase during fixing, thereby easily improving the image fixing strength.
[0079] (It should be noted that, hereinafter, the amorphous polyester resin contained in the core portion is referred to as "b2".)
[0080] From the perspective of easily improving the image fixing strength, the mass ratio of the amorphous resin (more preferably the amorphous polyester resin b2) contained in the core to the binding resin (i) (preferably the crystalline resin and the amorphous resin, more preferably the crystalline polyester resin a and the amorphous polyester resin b1) contained in the continuous phase (more preferably the mass ratio of the amorphous polyester resin b2 to the crystalline polyester resin a and the amorphous polyester resin b1 [b2 / (a+b1)]) is preferably 0.01 to 0.6, more preferably 0.02 to 0.3, and further preferably 0.03 to 0.1.
[0081] The amorphous resin (more preferably the amorphous polyester resin b2) contained in the core may be one kind or two or more kinds.
[0082] The content of the amorphous polyester resin b2 in the entire binder resin contained in the core portion is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 100% by mass.
[0083] Adhesive resin (iii) contained in the coating layer
[0084] The adhesive resin (iii) contained in the coating layer preferably has a different structure as a structural unit in the polymer chain relative to the adhesive resin (i) contained in the continuous phase and the adhesive resin (ii) contained in the core. By making the adhesive resin (iii) contained in the coating layer a resin having a different structure as a structural unit in the polymer chain relative to the adhesive resin contained in the continuous phase and the core, it is easy to form a structure (so-called sea-island structure) having a continuous phase and a discontinuous phase (the discontinuous phase has a core and a coating layer covering the core).
[0085] In addition, the adhesive resin (iii) contained in the coating layer preferably forms a chemical bond with the adhesive resin (ii) contained in the core at the interface between the core and the coating layer. By forming a chemical bond with the adhesive resin, a structure (so-called sea-island structure) having a continuous phase and a discontinuous phase (the discontinuous phase has a core and a coating layer covering the core) is easily formed.
[0086] As described above, the adhesive resin (iii) contained in the coating layer is preferably an adhesive resin having a different structure as a structural unit in the polymer chain relative to the adhesive resin (i) and the adhesive resin (ii), and preferably forms a chemical bond at the interface between the core and the coating layer relative to the adhesive resin (ii). In addition, from the aspect of easily forming a structure (so-called sea island structure) having a continuous phase and a discontinuous phase (the discontinuous phase has a core and a coating layer covering the core), it is preferred that the adhesive resin (iii) contained in the coating layer has low compatibility with the adhesive resin (i) and the adhesive resin (ii).
[0087] From this perspective, when the continuous phase contains crystalline polyester resin a and amorphous polyester resin b1 and the core contains amorphous polyester resin b2, the coating layer preferably contains a vinyl resin. (It should be noted that the vinyl resin contained in the coating layer is hereinafter referred to as "c.")
[0088] The adhesive resin (iii) (more preferably the vinyl resin c) contained in the coating layer preferably has a glass transition temperature Tg lower than the fixing temperature (i.e., the set temperature for fixing in the image forming apparatus). By making the glass transition temperature Tg of the adhesive resin (iii) (more preferably the vinyl resin c) lower than the fixing temperature, the amorphous resin in the core portion is easily dissolved from the discontinuous phase during fixing, and the image fixing strength is easily improved.
[0089] From the perspective of improving the image fixing strength, the glass transition temperature Tg of the binder resin (iii) contained in the covering layer is preferably from -70°C to 40°C, more preferably from -50°C to 30°C, and even more preferably from -40°C to 20°C.
[0090] The glass transition temperature Tg of the binder resin (iii) can be determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, by the "extrapolated glass transition start temperature" described in the method for measuring glass transition temperature in JIS K 7121-1987 "Methods for measuring transition temperatures of plastics".
[0091] In addition, the adhesive resin (more preferably the vinyl resin c) contained in the covering layer may be one kind or two or more kinds.
[0092] The content of the vinyl resin c in the entire adhesive resin contained in the covering layer is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 100% by mass.
[0093] Relationship between the adhesive resin (i) contained in the continuous phase and the adhesive resin (ii) contained in the core
[0094] In the case where the continuous phase contains an amorphous resin (more preferably an amorphous polyester resin b1) as a binding resin (i) and the core contains an amorphous resin (more preferably an amorphous polyester resin b2) as a binding resin (ii), the amorphous resin (more preferably an amorphous polyester resin b1 and b2) contained in the continuous phase and the core may be the same resin or different resins.
[0095] It should be noted that when the glass transition temperature Tg of the adhesive resin (iii) (more preferably the vinyl resin c) contained in the coating layer is lower than the fixing temperature, it is preferred that the amorphous resin (more preferably the amorphous polyester resins b1 and b2) contained in the continuous phase and the core have high compatibility with each other. Due to the high compatibility of the two, the amorphous resin in the core dissolves from the discontinuous phase during fixing and is compatible with the amorphous resin in the continuous phase, thereby easily improving the image fixing strength.
[0096] From the perspective of improving compatibility, the amorphous resin contained in the continuous phase and the amorphous resin contained in the core (more preferably amorphous polyester resin b1 and amorphous polyester resin b2) are preferably resins having only structural units of the same structure as structural units in the polymer chain (for example, synthesized using only monomers of the same molecular structure as raw materials for the resin).
[0097] In addition, the analysis of the structural unit which the resin has in the polymer chain can be obtained by analyzing using NMR.
[0098] Here, the method for forming a structure having a continuous phase and a discontinuous phase having a core and a coating layer is not particularly limited. For example, the following method based on the aggregation and coalescence (aggregation unification) method can be cited as an example.
[0099] First, a dispersion of resin particles of amorphous polyester resin b2 having unsaturated double bonds is prepared. A vinyl monomer and an initiator are added thereto to react, thereby preparing a dispersion of composite resin particles having a coating layer containing vinyl resin c around a core containing amorphous polyester resin b2. It should be noted that since the amorphous polyester resin b2 has unsaturated double bonds, chemical bonds are formed between it and the vinyl resin c at the interface between the core and the coating layer.
[0100] By using the composite resin particle dispersion and separately prepared resin particle dispersions of amorphous polyester resin b1 and crystalline polyester resin a to produce a toner by an aggregation method, a toner having a structure including a continuous phase and a discontinuous phase (the discontinuous phase having a core and a coating layer) can be obtained.
[0101] ·G' 50T , G' 100T and tanδ T Control method
[0102] In the toner having the structure of (1) above, as for the storage modulus G' 50T , storage modulus G' 100T and tanδ T As a method of performing control, for example, the following method can be mentioned.
[0103] For example, the storage modulus G' of the toner 50T The control method includes: adjusting the content of crystalline resin (preferably crystalline polyester resin A) contained in the continuous phase and the storage modulus G' at 50°C, the storage modulus G' at 50°C of the amorphous resin (preferably amorphous polyester resin b1) contained in the continuous phase, and the content of amorphous resin (preferably amorphous polyester resin b2) contained in the core and the storage modulus G' at 50°C.
[0104] In addition, the storage modulus G' of the toner 100TThe control method includes: adjusting the content of crystalline resin (preferably crystalline polyester resin A) contained in the continuous phase and the storage modulus G' at 100°C, the storage modulus G' at 100°C of the amorphous resin (preferably amorphous polyester resin b1) contained in the continuous phase, the content of amorphous resin (preferably amorphous polyester resin b2) contained in the core and the storage modulus G' at 100°C, the particle size (specifically, the average equivalent circle diameter) of the discontinuous phase having the core and the coating layer, and the thickness of the coating layer.
[0105] In addition, as the tan δ of the toner T The control method includes: adjusting the content of the crystalline resin (preferably the crystalline polyester resin A) contained in the continuous phase and the storage modulus G' and the loss modulus G" in the entire temperature range of 50°C to 100°C, the storage modulus G' and the loss modulus G" of the amorphous resin (preferably the amorphous polyester resin b1) contained in the continuous phase in the entire temperature range of 50°C to 100°C, the content of the amorphous resin (preferably the amorphous polyester resin b2) contained in the core and the storage modulus G' and the loss modulus G" in the entire temperature range of 50°C to 100°C, the particle size (specifically, the average equivalent circle diameter) of the discontinuous phase having the core and the coating layer, and the thickness of the coating layer.
[0106] In particular, by making the storage modulus G' and loss modulus G" of the crystalline resin (preferably the crystalline polyester resin A) contained in the continuous phase different from the storage modulus G' and loss modulus G" of the amorphous resin (preferably the amorphous polyester resin b1) contained in the continuous phase in the entire temperature range of 50°C to 100°C, it is easy to adjust the storage modulus G' of the toner to a desired value. 50T , storage modulus G' 100T and tanδ T Control within the above range.
[0107] G' and tanδ in each resin
[0108] In the toner having the structure of (1) above, the storage modulus G′ and the loss tangent tan δ of each resin contained in the continuous phase, the core portion, and the coating layer are preferably in the following ranges.
[0109] [1] Crystalline resin contained in the continuous phase (preferably crystalline polyester resin a)
[0110] From the storage modulus G' of the toner at 50°C 50T In order to control the above range, the crystalline resin (preferably crystalline polyester resin a) contained in the continuous phase has a storage modulus G′ at 50° C. in dynamic viscoelasticity measurement. 50aPreferably 1×10 6 Pa or above 1×10 9 Pa or less, more preferably 1×10 7 Pa or above 1×10 8 Below Pa.
[0111] From the storage modulus G' of the toner at 100°C 100T In order to control the above range, the crystalline resin (preferably crystalline polyester resin a) contained in the continuous phase has a storage modulus G′ at 100° C. in dynamic viscoelasticity measurement. 100a Preferably 1×10 -1 Pa or above 1×10 2 Pa or less, more preferably 1×10 0 Pa or above 1×10 1 Below Pa.
[0112] It is easy to adjust the tanδ of the toner over the entire temperature range of 50°C to 100°C. T In order to control the above range, the crystalline resin (preferably crystalline polyester resin a) contained in the continuous phase has a tan δ value of 50° C. or more and 50° C. or less in the entire temperature range of the melting temperature of the crystalline resin in the dynamic viscoelasticity measurement. a It is preferably 0.01 to 1.0, and more preferably 0.05 to 0.5.
[0113] The melting temperature of the crystalline resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, and even more preferably 60°C to 85°C.
[0114] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by the “melting peak temperature” described in the method for measuring the melting temperature of JIS K7121-1987 “Method for measuring transition temperatures of plastics”.
[0115] [2] Amorphous resin contained in the continuous phase (preferably amorphous polyester resin b1)
[0116] From the storage modulus G' of the toner at 50°C 50T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin b1) contained in the continuous phase has a storage modulus G′ at 50° C. in the dynamic viscoelasticity measurement. 50b1 Preferably 1×10 7 Pa above 2×10 9 Pa or less, more preferably 1×10 8 Pa or above 1×10 9 Below Pa.
[0117] From the storage modulus G' of the toner at 100°C 100T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin b1) contained in the continuous phase has a storage modulus G′ at 100° C. in a dynamic viscoelasticity measurement. 100b1 Preferably 1×10 3 Pa or above 1×10 6 Pa or less, more preferably 2×10 3 Pa above 2×10 5 Below Pa.
[0118] It is easy to adjust the tanδ of the toner over the entire temperature range of 50°C to 100°C. T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin b1) contained in the continuous phase has a tan δ value of 1.50°C in the entire temperature range of 50°C to 100°C in the dynamic viscoelasticity measurement. b1 It is preferably 0.001 to 4.0, and more preferably 0.001 to 2.0.
[0119] [3] Amorphous resin contained in the core (preferably amorphous polyester resin b2)
[0120] From the storage modulus G' of the toner at 50°C 50T In order to control the above range, the amorphous resin (preferably amorphous polyester resin b2) contained in the core has a storage modulus G′ at 50° C. in dynamic viscoelasticity measurement. 50b2 Preferably 1×10 4 Pa or above 1×10 7 Pa or less, more preferably 3×10 4 Pa above 3×10 5 Below Pa.
[0121] From the storage modulus G' of the toner at 100°C 100T In order to control the above range, the amorphous resin (preferably amorphous polyester resin b2) contained in the core has a storage modulus G′ at 100° C. in dynamic viscoelasticity measurement. 100b2 Preferably 1×10 3 Pa above 3×10 5 Pa or less, more preferably 1×10 4 Pa above 2×10 5 Below Pa.
[0122] It is easy to adjust the tanδ of the toner over the entire temperature range of 50°C to 100°C. TIn order to control the above range, the amorphous resin (preferably the amorphous polyester resin b2) contained in the core has a tan δ value of 1.5047 W / m2 over the entire temperature range of 50°C to 100°C in the dynamic viscoelasticity measurement. b2 It is preferably less than 1, and more preferably 0.1 to 0.6.
[0123] In addition, it is easy to adjust the tan δ of the toner in the entire temperature range of 50°C to 100°C. T In order to control the above range, the storage modulus G′ of the amorphous resin (preferably amorphous polyester resin b2) contained in the core is 50 -100b2 is preferably 1×10 3 Pa or above 1×10 7 Pa or less, more preferably 1×10 4 Above 3×10 5 Below Pa.
[0124] [4] Inclusions in the toner other than the amorphous resin (preferably the amorphous polyester resin b2) contained in the core portion
[0125] From the storage modulus G' of the toner at 50°C 50T In order to control the content within the above range, the storage modulus G′ of the toner other than the amorphous resin (preferably the amorphous polyester resin b2) contained in the core is 0.0447 W / m in a dynamic viscoelasticity measurement at 50° C. 50r Preferably 3×10 6 Pa above 9×10 8 Pa or less, more preferably 4×10 6 Pa above 7×10 8 Pa or less, more preferably 1×10 8 Pa above 5×10 8 Below Pa.
[0126] From the storage modulus G' of the toner at 100°C 100T In order to control the content of the toner to fall within the above range, the storage modulus G′ of the toner other than the amorphous resin (preferably the amorphous polyester resin b2) contained in the core portion at 100° C. in the dynamic viscoelasticity measurement is 100r Preferably 1×10 3 Pa or above 1×10 5 Pa or less, more preferably 1×10 3 Pa above 3×10 4 Below Pa.
[0127] It should be noted that the measurements of the above-mentioned physical properties of the crystalline resin (preferably crystalline polyester resin a) contained in the continuous phase, the amorphous resin (preferably amorphous polyester resin b1) contained in the continuous phase, the amorphous resin (preferably amorphous polyester resin b2) contained in the core, and the contents contained in the toner other than the amorphous resin (preferably amorphous polyester resin b2) contained in the core, can be performed on the resins serving as the raw materials before the manufacture of the toner, or can be performed after separating the resins from the toner.
[0128] In addition, the storage modulus G' at 50°C, the storage modulus G' at 100°C, the storage modulus G' in the entire temperature range of 50°C to 100°C, and the tanδ in the entire temperature range of 50°C to 100°C of each resin can be measured according to the method described in the above-mentioned "Measurement of dynamic viscoelasticity of toner".
[0129] Here, a method for separating each resin (preferably the crystalline polyester resin a, the non-crystalline polyester resin b1, and the non-crystalline polyester resin b2) contained in the continuous phase, the core portion, and the coating layer in the toner will be described.
[0130] Method for separating crystalline polyester resin a
[0131] (1) 0.25 g of the toner is weighed, 40 mL of tetrahydrofuran (THF) is added thereto, and the mixture is mixed and stirred for 3 hours.
[0132] (2) The mixed solution obtained in (1) was separated using a centrifugal separator at 2000 rpm for 30 minutes.
[0133] (3) The precipitate obtained after centrifugation in (2) was taken out and washed with methanol to remove THF.
[0134] (4) The washed precipitate is transferred to an aluminum pan or the like, and dried in a vacuum dryer adjusted to 50° C. to evaporate the methanol component.
[0135] (5) To the dried substance was added 40 mL of THF, and the mixture was mixed and stirred for 1 hour while heating to 85°C.
[0136] (6) The mixed solution obtained in (5) is filtered without cooling to remove the supernatant. The obtained supernatant is transferred to an aluminum pan or the like, and the THF component is evaporated and dried in a vacuum dryer adjusted to 50° C. to obtain a crystalline polyester resin a separated from the toner.
[0137] Method for separating amorphous polyester resin b1
[0138] (1) 0.25 g of the toner is weighed, 40 mL of tetrahydrofuran (THF) is added thereto, and the mixture is mixed and stirred for 3 hours.
[0139] (2) The mixed solution obtained in (1) was separated using a centrifugal separator at 2000 rpm for 30 minutes.
[0140] (3) The supernatant after centrifugation obtained in (2) is transferred to an aluminum pan or the like, and the methanol component is evaporated and dried in a vacuum dryer adjusted to 50° C. to obtain amorphous polyester resin b1 separated from the toner.
[0141] Method for separating amorphous polyester resin b2
[0142] (1) 0.25 g of the toner is weighed, 40 mL of tetrahydrofuran (THF) is added thereto, and the mixture is mixed and stirred for 3 hours.
[0143] (2) The mixed solution obtained in (1) was separated using a centrifugal separator at 2000 rpm for 30 minutes.
[0144] (3) The precipitate obtained after centrifugation in (2) was taken out and washed with methanol to remove THF.
[0145] (4) The washed precipitate is transferred to an aluminum pan or the like, and dried in a vacuum dryer adjusted to 50° C. to evaporate the methanol component.
[0146] (5) To the dried substance was added 40 mL of THF, and the mixture was mixed and stirred for 1 hour while heating to 85°C.
[0147] (6) The mixed solution obtained in (5) is filtered without cooling to remove the THF insoluble component. The THF insoluble component is transferred to an aluminum plate or the like, and the THF component is evaporated and dried in a vacuum dryer adjusted to 50° C. to obtain a non-crystalline polyester resin b2 separated from the toner.
[0148] · Particle size of discontinuous phase (average equivalent circle diameter)
[0149] It is easy to convert the storage modulus G' of the toner 100T and tanδ T From the viewpoint of controlling within the above range, the average equivalent circle diameter (L1) of the discontinuous phase is preferably 100 nm to 300 nm, more preferably 150 nm to 250 nm, and even more preferably 180 nm to 220 nm.
[0150] ·Thickness of coating layer (average thickness)
[0151] It is easy to convert the storage modulus G' of the toner100T and tanδ T From the viewpoint of controlling within the above range, the average thickness (L2) of the coating layer is preferably 20 nm to 50 nm, more preferably 30 nm to 45 nm, and even more preferably 35 nm to 40 nm.
[0152] Here, a method for measuring the average equivalent circle diameter of the discontinuous phase by cross-sectional observation of the toner will be described.
[0153] First, the toner particles are embedded with bisphenol A type liquid epoxy resin and a curing agent to prepare a cutting sample. Then, the cutting sample is cut at -100°C using a cutting machine using a diamond knife (e.g., LEICA ULTRA Microtome, manufactured by Hitachi High-Technologies Co., Ltd.) to prepare an observation sample. Furthermore, in the case of wishing to increase the brightness difference (contrast) described later, the observation sample can be placed in a dryer under a ruthenium tetroxide atmosphere and dyed. It should be noted that the judgment of dyeing is determined by the dyeing state of the belt placed in the dryer.
[0154] The observation sample thus obtained was observed using a scanning transmission electron microscope (STEM). An image was recorded at a magnification such that a cross section of one toner particle entered the field of view. The recorded image was analyzed using image analysis software (WinROOF, manufactured by Mitani Shoji Co., Ltd.) at a condition of 0.010000 μm / pixel. Through this image analysis, the cross-sectional shape of the discontinuous phase was extracted based on the brightness difference (contrast) between the adhesive resin of the continuous phase (sea) of the toner particles and the adhesive resin of the discontinuous phase (island) having a core and a coating layer.
[0155] Then, the projected area is calculated based on the extracted cross-sectional shape of the discontinuous phase. The equivalent circular diameter of the discontinuous phase is calculated from the projected area. It should be noted that the equivalent circular diameter is calculated by the formula “2×(projected area / π) 1 / 2 ” is calculated. 100 toners are observed, each discontinuous phase is selected one by one, its equivalent circle diameter is calculated, and its arithmetic mean is taken as the average equivalent circle diameter (L1) of the discontinuous phase.
[0156] In addition, the cross-sectional shape of the core is extracted from the brightness difference (contrast) between the adhesive resin of the core and the adhesive resin of the coating layer. Based on the cross-sectional shape of the core, the projection area of the core is calculated, and the equivalent circular diameter of the core is further calculated. It should be noted that 100 toners are observed in the same way as (L1) above, and each core is selected one by one to calculate its equivalent circular diameter, and the arithmetic mean thereof is used as the average equivalent circular diameter (L3) of the core. Then, the average thickness (L2) of the coating layer is calculated from the difference between (L1) and (L3) by the formula "(L1-L3) / 2)".
[0157] (2) Toner containing a tetrahydrofuran (THF) insoluble component, wherein the THF insoluble component forms a discontinuous phase
[0158] The toner having the structure of (2) above has a continuous phase containing a binder resin (I) and a discontinuous phase dispersed in the continuous phase and containing a binder resin (II), and the binder resin (II) contains a THF-insoluble component. That is, the continuous phase corresponding to the sea and the discontinuous phase corresponding to the islands (regions) form a so-called sea-island structure.
[0159] -Binder resin contained in the continuous phase and the discontinuous phase-
[0160] The binder resin (I) contained in the continuous phase and the binder resin (II) contained in the discontinuous phase are not particularly limited. It is preferred that the binder resin (I) is a resin substantially free of THF-insoluble components, while the binder resin (II) is a resin containing THF-insoluble components.
[0161] It should be noted that “substantially containing no THF-insoluble components” means that the content of the THF-insoluble components is 1.0% by mass or less (more preferably 0.5% by mass or less).
[0162] In addition, the adhesive resin (I) and the adhesive resin (II) may be different resins (for example, resins having different structures as structural units in the polymer chain (for example, resins synthesized using monomers of different molecular structures as raw materials for the resin); resins having structural units in the polymer chain of the same structure but different average molecular weights; etc.), or they may be the same resin, except for the presence or absence of THF insoluble components.
[0163] ·Binder resin (I) contained in the continuous phase
[0164] The continuous phase preferably contains a crystalline resin and an amorphous resin as the binder resin (I). By containing a crystalline resin in the continuous phase, it is easy to improve the low-temperature fixability. It should be noted that, from the perspective of improving the low-temperature fixability, it is more preferred that the continuous phase contains a crystalline polyester resin and an amorphous polyester resin. (It should be noted that, hereinafter, the crystalline polyester resin contained in the continuous phase is recorded as "A", and the amorphous polyester resin contained in the continuous phase is recorded as "B1".)
[0165] The mass ratio of the crystalline resin to the non-crystalline resin contained in the continuous phase (more preferably the mass ratio (A / B1) of the crystalline polyester resin A to the non-crystalline polyester resin B1) is preferably 0.04 to 1.0, more preferably 0.09 to 0.6, and further preferably 0.1 to 0.4.
[0166] By making the mass ratio of the crystalline resin to the amorphous resin (more preferably the mass ratio of the crystalline polyester resin A to the amorphous polyester resin B1 (A / B1)) to be 0.04 or more, it is easy to improve the low-temperature fixing property; on the other hand, by making the mass ratio to be 1.0 or less, it is easy to improve the image fixing strength.
[0167] It should be noted that the crystalline resin and the amorphous resin contained in the continuous phase may be one type or two or more types, respectively. In addition, the crystalline polyester resin A and the amorphous polyester resin B1 contained in the continuous phase may be one type or two or more types, respectively.
[0168] The total content of the crystalline polyester resin A and the amorphous polyester resin B1 in the entire binder resin contained in the continuous phase is preferably 50% by mass or more, more preferably 80% by mass or more, and further preferably 100% by mass.
[0169] ·Binder resin (II) contained in the discontinuous phase
[0170] The discontinuous phase preferably contains a non-crystalline resin (more preferably a non-crystalline polyester resin) as the binder resin (II). Furthermore, the non-crystalline resin preferably contains a THF-insoluble component.
[0171] (It should be noted that, hereinafter, the amorphous polyester resin contained in the discontinuous phase is referred to as "B2".)
[0172] The content of the tetrahydrofuran-insoluble component in the amorphous resin (more preferably the amorphous polyester resin B2) contained in the discontinuous phase is preferably 90 mass % to 100 mass %, more preferably 92 mass % to 98 mass %, further preferably 94 mass % to 96 mass %.
[0173] It should be noted that the tetrahydrofuran (THF) insoluble component represents a solid component derived from the resin, that is, it is considered to represent a gel-like resin component that has formed a cross-linked structure. By setting the content of the tetrahydrofuran insoluble component to the above range, it is easy to form a structure that exists in a dispersed state as a discontinuous phase (region) in the toner particles, and it is easy to increase the storage modulus G' of the toner at 50°C. 50T , Storage modulus G' at 100℃ 100T , tanδ in the entire temperature range from 50℃ to 100℃ T Control within the above range.
[0174] Here, the method for measuring the content of the tetrahydrofuran (THF) insoluble component is described.
[0175] The THF-insoluble content may be measured for the resin used as a raw material before the production of the toner, or may be measured after each resin is separated from the toner.
[0176] The separation method is as described above.
[0177] Then, the content of the THF-insoluble component was determined by the following method.
[0178] (1) 0.25 g of a resin was weighed, 40 mL of tetrahydrofuran was added thereto, and the mixture was mixed and stirred for 3 hours.
[0179] (2) Then, the mixed solution obtained in (1) was separated using a centrifugal separator at 2000 rpm for 30 minutes.
[0180] (3) 5 mL of the supernatant obtained after centrifugation in (2) was weighed and transferred to an aluminum pan. The THF component was evaporated and dried in a vacuum dryer adjusted to 50°C.
[0181] (4) The THF insoluble component was calculated by the following formula from the difference in mass of the aluminum pan before and after drying.
[0182] THF insoluble components [%] = {0.25 - [(mass of supernatant and aluminum plate) - (mass of aluminum plate after drying) × 8}] / 0.25 × 100
[0183] The non-crystalline resin (more preferably the non-crystalline polyester resin B2) contained in the discontinuous phase may be one kind or two or more kinds.
[0184] The content of the non-crystalline polyester resin B2 in the entire binder resin contained in the discontinuous phase is preferably 50% by mass or more, more preferably 80% by mass or more, and even more preferably 100% by mass.
[0185] ·G'50T , G' 100T and tanδ T Control method
[0186] In the toner having the structure (2) above, as for the storage modulus G' 50T , storage modulus G' 100T and tanδ T As a method of performing control, for example, the following method can be mentioned.
[0187] For example, the storage modulus G' of the toner 50T The control method includes: adjusting the content of the crystalline resin (preferably the crystalline polyester resin A) contained in the continuous phase and the storage modulus G' at 50°C, the storage modulus G' at 50°C of the amorphous resin (preferably the amorphous polyester resin B1) contained in the continuous phase, and the content of the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase and the storage modulus G' at 50°C.
[0188] In addition, the storage modulus G' of the toner 100T The control method includes: adjusting the content of the crystalline resin (preferably the crystalline polyester resin A) contained in the continuous phase and the storage modulus G' at 100°C, the storage modulus G' at 100°C of the amorphous resin (preferably the amorphous polyester resin B1) contained in the continuous phase, the content of the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase and the storage modulus G' at 100°C, and the particle size (specifically, the average equivalent circle diameter) of the discontinuous phase.
[0189] In addition, as the tan δ of the toner T The control method includes: adjusting the content of the crystalline resin (preferably the crystalline polyester resin A) contained in the continuous phase and the storage modulus G' and the loss modulus G" in the entire temperature range of 50°C to 100°C, the storage modulus G' and the loss modulus G" of the amorphous resin (preferably the amorphous polyester resin B1) contained in the continuous phase in the entire temperature range of 50°C to 100°C, the content of the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase and the storage modulus G' and the loss modulus G" in the entire temperature range of 50°C to 100°C, and the particle size of the discontinuous phase (specifically, the average equivalent circle diameter).
[0190] In particular, by making the storage modulus G' and loss modulus G" of the crystalline resin (preferably the crystalline polyester resin A) contained in the continuous phase different from the storage modulus G' and loss modulus G" of the amorphous resin (preferably the amorphous polyester resin B1) contained in the continuous phase in the entire temperature range of 50°C to 100°C, it is easy to adjust the storage modulus G' of the toner to a desired value. 50T , storage modulus G' 100T and tanδ T Control within the above range.
[0191] G' and tanδ in each resin
[0192] In the toner having the structure of (2) above, the preferred ranges of the storage modulus G′ and the loss tangent tan δ of each resin contained in the continuous phase and the discontinuous phase are as follows.
[0193] [1] Crystalline resin contained in the continuous phase (preferably crystalline polyester resin A)
[0194] From the storage modulus G' of the toner at 50°C 50T In order to control the above range, the crystalline resin (preferably crystalline polyester resin A) contained in the continuous phase has a storage modulus G′ at 50° C. in the dynamic viscoelasticity measurement. 50A Preferably 1×10 6 Pa or above 1×10 9 Pa or less, more preferably 1×10 7 Pa or above 1×10 8 Below Pa.
[0195] From the storage modulus G' of the toner at 100°C 100T In order to control the above range, the crystalline resin (preferably crystalline polyester resin A) contained in the continuous phase has a storage modulus G′ at 100° C. in dynamic viscoelasticity measurement. 100A Preferably 1×10 -1 Pa or above 1×10 2 Pa or less, more preferably 1×10 0 Pa or above 1×10 1 Below Pa.
[0196] It is easy to adjust the tanδ of the toner over the entire temperature range of 50°C to 100°C. T In order to control the above range, the crystalline resin (preferably the crystalline polyester resin A) contained in the continuous phase has a tan δ value of 50° C. or more and 50° C. or less in the entire temperature range of the melting temperature of the crystalline resin in the dynamic viscoelasticity measurement. AIt is preferably 0.01 to 1.0, and more preferably 0.05 to 0.5.
[0197] The melting temperature of the crystalline resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, and even more preferably 60°C to 85°C.
[0198] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by the “melting peak temperature” described in the method for measuring the melting temperature of JIS K7121-1987 “Method for measuring transition temperatures of plastics”.
[0199] [2] Amorphous resin contained in the continuous phase (preferably amorphous polyester resin B1)
[0200] From the storage modulus G' of the toner at 50°C 50T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin B1) contained in the continuous phase has a storage modulus G′ at 50° C. in the dynamic viscoelasticity measurement. 50B1 Preferably 1×10 7 Pa above 2×10 9 Pa or less, more preferably 1×10 8 Pa or above 1×10 9 Below Pa.
[0201] From the storage modulus G' of the toner at 100°C 100T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin B1) contained in the continuous phase has a storage modulus G′ at 100° C. in dynamic viscoelasticity measurement. 100B1 Preferably 1×10 3 Pa or above 1×10 6 Pa or less, more preferably 2×10 3 Pa above 2×10 5 Below Pa.
[0202] It is easy to adjust the tanδ of the toner over the entire temperature range of 50°C to 100°C. T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin B1) contained in the continuous phase has a tan δ value of 1.50°C in the entire temperature range of 50°C to 100°C in the dynamic viscoelasticity measurement. B1 It is preferably 0.001 to 4.0, and more preferably 0.001 to 2.0.
[0203] [3] Amorphous resin contained in the discontinuous phase (preferably amorphous polyester resin B2)
[0204] From the storage modulus G' of the toner at 50°C 50T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase has a storage modulus G′ at 50° C. in dynamic viscoelasticity measurement. 50B2 Preferably 1×10 4 Pa or above 1×10 7 Pa or less, more preferably 1×10 4 Above 1×10 6 Below Pa.
[0205] From the storage modulus G' of the toner at 100°C 100T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase has a storage modulus G′ at 100° C. in dynamic viscoelasticity measurement. 100B2 Preferably 1×10 4 Pa or above 1×10 7 Pa or less, more preferably 1×10 4 Above 1×10 6 Below Pa.
[0206] It is easy to adjust the tanδ of the toner over the entire temperature range of 50°C to 100°C. T In order to control the above range, the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase has a tan δ value of 1.5047 W / m2 over the entire temperature range of 50°C to 100°C in the dynamic viscoelasticity measurement. B2 It is preferably less than 1, and more preferably 0.1 to 0.6.
[0207] In addition, it is easy to adjust the tan δ of the toner in the entire temperature range of 50°C to 100°C. T In order to control the above range, the storage modulus G′ of the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase in the whole temperature range of 50° C. to 100° C. in the dynamic viscoelasticity measurement is 50 -100B2 is preferably 1×10 3 Pa or above 1×10 7 Pa or less, more preferably 1×10 4 Pa or above 1×10 7 Pa or less, more preferably 1×10 4 Above 1×10 6 Below Pa.
[0208] [4] Ingredients contained in the toner other than the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase
[0209] From the storage modulus G' of the toner at 50°C 50T In order to control the content within the above range, the storage modulus G′ of the toner other than the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase at 50° C. in the dynamic viscoelasticity measurement is 50R Preferably 3×10 6 Pa above 9×10 8 Pa or less, more preferably 4×10 6 Pa above 7×10 8 Below Pa.
[0210] From the storage modulus G' of the toner at 100°C 100T In order to control the above range, the storage modulus G′ of the toner other than the amorphous resin (preferably the amorphous polyester resin B2) contained in the discontinuous phase in the dynamic viscoelasticity measurement at 100° C. 100R Preferably 1×10 3 Pa or above 1×10 5 Pa or less, more preferably 1×10 3 Pa above 3×10 4 Below Pa.
[0211] It should be noted that the measurements of the above-mentioned physical properties of the crystalline resin contained in the continuous phase (preferably crystalline polyester resin A), the amorphous resin contained in the continuous phase (preferably amorphous polyester resin B1), the amorphous resin contained in the discontinuous phase (preferably amorphous polyester resin B2), and the contents contained in the toner other than the amorphous resin contained in the discontinuous phase (preferably amorphous polyester resin B2) can be performed on the resins that serve as the raw materials before the manufacture of the toner, or can be performed after the resins are separated from the toner.
[0212] The separation method is as described above.
[0213] In addition, the storage modulus G' at 50°C, the storage modulus G' at 100°C, the storage modulus G' in the entire temperature range of 50°C to 100°C, and the tanδ in the entire temperature range of 50°C to 100°C of each resin were measured according to the method described in the above-mentioned "Measurement of dynamic viscoelasticity of toner".
[0214] · Particle size of discontinuous phase (average equivalent circle diameter)
[0215] It is easy to convert the storage modulus G' of the toner 100T and tanδ TFrom the perspective of controlling within the above range, the average equivalent circle diameter (L2) of the discontinuous phase is preferably 100 nm to 300 nm, more preferably 150 nm to 250 nm, and even more preferably 180 nm to 220 nm.
[0216] It should be noted that the method for measuring the average equivalent circle diameter (L2) is carried out in accordance with the method for measuring the average equivalent circle diameter (L1) described above.
[0217] Next, each component constituting the toner according to the present embodiment will be described in detail.
[0218] The toner according to the present embodiment includes toner particles and, if necessary, an external additive.
[0219] (Toner particles)
[0220] The toner particles include, for example, a binder resin and, if necessary, a colorant, a release agent, and other additives.
[0221] - Adhesive resin -
[0222] Examples of the adhesive resin include vinyl resins formed by homopolymers of the following monomers or copolymers of two or more of these monomers: styrenes (e.g., styrene, p-chlorostyrene, α-methylstyrene, etc.), (meth)acrylates (e.g., methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, lauryl acrylate, 2-ethylhexyl acrylate, methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, lauryl methacrylate, 2-ethylhexyl methacrylate, etc.), ethylenically unsaturated nitriles (e.g., acrylonitrile, methacrylonitrile, etc.), vinyl ethers (e.g., vinyl methyl ether, vinyl isobutyl ether, etc.), vinyl ketones (e.g., vinyl methyl ketone, vinyl ethyl ketone, vinyl isopropenyl ketone, etc.), olefins (e.g., ethylene, propylene, butadiene, etc.), and the like.
[0223] Examples of the adhesive resin include non-vinyl resins such as epoxy resins, polyester resins, polyurethane resins, polyamide resins, cellulose resins, polyether resins, and modified rosins, mixtures of these resins with the above-mentioned vinyl resins, or graft polymers obtained by polymerizing vinyl monomers in the coexistence of these resins.
[0224] These adhesive resins may be used alone or in combination of two or more.
[0225] It should be noted that, although not particularly limited, when the toner particles of the present embodiment are toner particles in a toner having the structure (1) described above, it is preferred that the continuous phase contains crystalline polyester resin a and amorphous polyester resin b1, the core contains amorphous polyester resin b2, and the coating layer contains a vinyl resin.
[0226] When the toner particles of the present embodiment are toner particles in the toner having the structure (2) above, the continuous phase preferably contains the crystalline polyester resin A and the amorphous polyester resin B1, and the discontinuous phase preferably contains the amorphous polyester resin B2 containing a THF-insoluble component.
[0227] As the polyester resin, for example, a known amorphous polyester resin can be cited. Among the polyester resins, an amorphous polyester resin and a crystalline polyester resin can be used together. However, the crystalline polyester resin can be used in a content range of 2 mass % to 40 mass % (preferably 2 mass % to 20 mass %) relative to the total binding resin in the toner.
[0228] It should be noted that the "crystallinity" of a resin means that there is no step-like change in endothermic value in differential scanning calorimetry (DSC) and that there is a clear endothermic peak. Specifically, it means that the half-width of the endothermic peak when measured at a heating rate of 10 (°C / min) is within 10°C.
[0229] On the other hand, the "amorphous" nature of a resin means that the half-peak width is larger than 10°C, the endothermic value shows a step-like change, or a clear endothermic peak is not confirmed.
[0230] Amorphous polyester resin
[0231] Examples of the amorphous polyester resin include polycondensates of polycarboxylic acids and polyols. As the amorphous polyester resin, a commercially available product may be used, or a synthetic product may be used.
[0232] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, malonic acid, maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, succinic acid, alkenyl succinic acid, adipic acid, sebacic acid, etc.), alicyclic dicarboxylic acids (e.g., cyclohexane dicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., terephthalic acid, isophthalic acid, phthalic acid, naphthalene dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof. Among these, aromatic dicarboxylic acids are preferred as the polycarboxylic acid.
[0233] Among the polycarboxylic acids, dicarboxylic acids and trivalent or higher carboxylic acids having a crosslinked structure or a branched structure may be used in combination. Examples of trivalent or higher carboxylic acids include trimellitic acid, pyromellitic acid, their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.
[0234] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0235] Examples of the polyol include aliphatic diols (e.g., ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol, butanediol, hexanediol, neopentyl glycol, etc.), alicyclic diols (e.g., cyclohexanediol, cyclohexanedimethanol, hydrogenated bisphenol A, etc.), and aromatic diols (e.g., ethylene oxide adducts of bisphenol A, propylene oxide adducts of bisphenol A, etc.). Among these, the polyol is preferably an aromatic diol or an alicyclic diol, and more preferably an aromatic diol.
[0236] As the polyol, a diol may be used in combination with a trivalent or higher polyol having a crosslinked structure or a branched structure. Examples of the trivalent or higher polyol include glycerin, trimethylolpropane, and pentaerythritol.
[0237] The polyols may be used alone or in combination of two or more.
[0238] The glass transition temperature (Tg) of the amorphous polyester resin is preferably 50°C to 80°C, and more preferably 50°C to 65°C.
[0239] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC), more specifically, according to the "extrapolated glass transition start temperature" described in the method for measuring glass transition temperature in JIS K 7121-1987 "Method for measuring transition temperature of plastics".
[0240] The weight average molecular weight (Mw) of the amorphous polyester resin is preferably 5,000 to 1,000,000, and more preferably 7,000 to 500,000.
[0241] The number average molecular weight (Mn) of the amorphous polyester resin is preferably 2,000 or more and 100,000 or less.
[0242] The molecular weight distribution Mw / Mn of the amorphous polyester resin is preferably 1.5 or more and 100 or less, and more preferably 2 or more and 60 or less.
[0243] It should be noted that the weight average molecular weight and the number average molecular weight are measured by gel permeation chromatography (GPC). In the molecular weight measurement using GPC, a Tosoh GPC HLC-8120GPC is used as a measuring device, a Tosoh column TSK gel Super HM-M (15 cm) is used, and the measurement is performed using a THF solvent. The weight average molecular weight and the number average molecular weight are calculated based on the measurement results using a molecular weight calibration curve prepared using a monodisperse polystyrene standard sample.
[0244] The amorphous polyester resin is obtained by a known production method. Specifically, for example, the amorphous polyester resin is obtained by setting the polymerization temperature to 180° C. to 230° C., reducing the pressure in the reaction system as necessary, and reacting while removing water or alcohol generated during condensation.
[0245] It should be noted that, when the monomer of the raw material is insoluble or incompatible at the reaction temperature, a high boiling point solvent may be added as a dissolving aid to dissolve it. In this case, the dissolving aid is removed by distillation while the polycondensation reaction is carried out. In the case of the presence of a monomer with poor compatibility in the copolymerization reaction, the monomer with poor compatibility may be condensed with a specific acid or alcohol that is polycondensed with the monomer in advance, and then polycondensed with the main component.
[0246] Crystalline polyester resin
[0247] Examples of the crystalline polyester resin include polycondensates of polycarboxylic acids and polyols. As the crystalline polyester resin, a commercially available product may be used, or a synthetic product may be used.
[0248] Here, in order to make the crystalline polyester resin easily form a crystal structure, the crystalline polyester resin is preferably a polycondensate obtained using a linear aliphatic polymerizable monomer rather than a polycondensate obtained using a polymerizable monomer having an aromatic group.
[0249] Examples of the polycarboxylic acid include aliphatic dicarboxylic acids (e.g., oxalic acid, succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, 1,9-nonanedicarboxylic acid, 1,10-decanedicarboxylic acid, 1,12-dodecanedicarboxylic acid, 1,14-tetradecanedicarboxylic acid, 1,18-octadecanedicarboxylic acid, etc.), aromatic dicarboxylic acids (e.g., dibasic acids such as phthalic acid, isophthalic acid, terephthalic acid, and naphthalene-2,6-dicarboxylic acid, etc.), anhydrides thereof, or lower (e.g., carbon number 1 to 5) alkyl esters thereof.
[0250] Among the polycarboxylic acids, dicarboxylic acids and trivalent or higher carboxylic acids having a crosslinked structure or a branched structure may be used in combination. Examples of trivalent carboxylic acids include aromatic carboxylic acids (e.g., 1,2,3-benzenetricarboxylic acid, 1,2,4-benzenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, etc.), their anhydrides, or their lower (e.g., carbon number 1 to 5) alkyl esters.
[0251] As the polycarboxylic acid, these dicarboxylic acids may be used in combination with a dicarboxylic acid having a sulfonic acid group or a dicarboxylic acid having an ethylenic double bond.
[0252] The polyvalent carboxylic acid may be used alone or in combination of two or more.
[0253] Examples of the polyol include aliphatic diols (e.g., linear aliphatic diols having a main chain portion having carbon atoms of 7 or more and 20 or less). Examples of the aliphatic diols include ethylene glycol, 1,3-propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,7-heptanediol, 1,8-octanediol, 1,9-nonanediol, 1,10-decanediol, 1,11-undecanediol, 1,12-dodecanediol, 1,13-tridecanediol, 1,14-tetradecanediol, 1,18-octadecanediol, and 1,14-eicosandiolus. Among these, preferred aliphatic diols include 1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol.
[0254] Among the polyols, diols may be used in combination with trivalent or higher alcohols having a crosslinked structure or a branched structure. Examples of the trivalent or higher alcohols include glycerin, trimethylolethane, trimethylolpropane, and pentaerythritol.
[0255] The polyols may be used alone or in combination of two or more.
[0256] Here, the content of the aliphatic diol in the polyol may be 80 mol % or more, and preferably 90 mol % or more.
[0257] The melting temperature of the crystalline polyester resin is preferably 50°C to 100°C, more preferably 55°C to 90°C, and even more preferably 60°C to 85°C.
[0258] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by the “melting peak temperature” described in the method for measuring melting temperature in JIS K7121-1987 “Method for measuring transition temperatures of plastics”.
[0259] The weight average molecular weight (Mw) of the crystalline polyester resin is preferably 6,000 or more and 35,000 or less.
[0260] The crystalline polyester resin can be obtained, for example, by a known production method similar to the amorphous polyester.
[0261] ·Vinyl resin
[0262] Vinyl resin is a vinyl monomer (i.e., a vinyl group (CH 2 =C(-R B1 )- / Here R B1 A polymer formed by polymerization of monomers containing only hydrogen atoms or methyl groups.
[0263] It should be noted that the term “(meth)acrylic acid” in the present specification includes both “acrylic acid” and “methacrylic acid”.
[0264] Examples of the vinyl monomer include (meth)acrylic acid and (meth)acrylic acid esters. Examples of the (meth)acrylic acid esters include (meth)acrylic acid alkyl esters (e.g., methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, n-butyl (meth)acrylate, n-pentyl (meth)acrylate, n-hexyl (meth)acrylate, n-heptyl (meth)acrylate, n-octyl (meth)acrylate, n-decyl (meth)acrylate, n-dodecyl (meth)acrylate, n-lauryl (meth)acrylate, n-tetradecyl (meth)acrylate, n-hexadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isopropyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, isoamyl (meth)acrylate, pentyl (meth)acrylate, neopentyl (meth)acrylate, isohexyl (meth)acrylate, isoheptyl (meth)acrylate, isooctyl (meth)acrylate, -
[0063] The invention also includes but is not limited to: (i) 2-ethylhexyl (meth)acrylate, (ii) cyclohexyl (meth)acrylate, (iii) tert-butylcyclohexyl (meth)acrylate, etc.), (iv) aryl (meth)acrylates (e.g., (v) phenyl (meth)acrylate, (iv) biphenyl (meth)acrylate, (iv) diphenylethyl (meth)acrylate, (iv) tert-butylphenyl (meth)acrylate, etc.), (v) dimethylaminoethyl (meth)acrylate, (iv) diethylaminoethyl (meth)acrylate, (iv) methoxyethyl (meth)acrylate, (iv) 2-hydroxyethyl (meth)acrylate, (v) β-carboxyethyl (meth)acrylate, (meth)acrylamide, styrene, alkyl-substituted styrene (e.g., (v) α-methylstyrene, 2-methylstyrene, 3-methylstyrene, 4-methylstyrene, 2-ethylstyrene, 3-ethylstyrene, 4-ethylstyrene, etc.), (v) halogen-substituted styrene (e.g., 2-chlorostyrene, 3-chlorostyrene, 4-chlorostyrene, etc.), and vinylnaphthalene.
[0265] In addition, a vinyl monomer having two or more functional groups (preferably a polyfunctional vinyl monomer having two or more vinyl groups) is also used.
[0266] Examples of the bifunctional vinyl monomer include divinylbenzene, divinylnaphthalene, di(meth)acrylate compounds (e.g., diethylene glycol di(meth)acrylate, methylenebis(meth)acrylamide, decanediol diacrylate, glycidyl(meth)acrylate, etc.), polyester di(meth)acrylate, and 2-([1'-methylpropyleneamino]carboxyamino)ethyl methacrylate.
[0267] Examples of the trifunctional or higher vinyl monomers include tri(meth)acrylate compounds (e.g., pentaerythritol tri(meth)acrylate, trimethylolethane tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, etc.), tetra(meth)acrylate compounds (e.g., pentaerythritol tetra(meth)acrylate, oligoester (meth)acrylate, etc.), 2,2-bis(4-methacryloyloxy, polyethoxyphenyl)propane, diallyl phthalate, triallyl cyanurate, triallyl isocyanurate, triallyl trimellitate, diaryl chlorendic acid, and the like.
[0268] The vinyl monomer is preferably a (meth)acrylate having an alkyl group with 2 to 14 carbon atoms (preferably 2 to 10 carbon atoms, more preferably 3 to 8 carbon atoms) from the viewpoint of fixability.
[0269] The vinyl monomers may be used alone or in combination of two or more.
[0270] When the covering layer contains a vinyl monomer, it is preferred that the glass transition temperature Tg thereof is lower than the fixing temperature (ie, the set temperature for fixing in the image forming apparatus).
[0271] The content of the binder resin is, for example, preferably 40% by mass to 95% by mass, more preferably 50% by mass to 90% by mass, and further preferably 60% by mass to 85% by mass, based on the entire toner particles.
[0272] -Colorants-
[0273] Examples of colorants include carbon black, chrome yellow, Hansa yellow, benzidine yellow, vat yellow, quinoline yellow, pigment yellow, permanent orange GTR, pyrazolone orange, sulfur-resistant orange, Wochug red, permanent red, brilliant carmine 3B, brilliant carmine 6B, DuPont Oil Red, pyrazolone red, litho red, rhodamine B lake, lake red C, pigment red, rose red, aniline blue, ultramarine blue, oil-soluble blue, methylene blue chloride, phthalocyanine blue, pigment blue, phthalocyanine green, malachite green oxalate and other pigments; or acridine-based, xanthene-based, azo-based, benzoquinone-based, azine-based, anthraquinone-based, thioindigo-based, dioxazine-based, thiazine-based, azomethine-based, indigo-based, phthalocyanine-based, nigrosine-based, polymethine-based, triphenylmethane-based, diphenylmethane-based, thiazole-based and other dyes; and the like.
[0274] In addition, a white pigment may be included as a colorant. Examples of the white pigment include titanium oxide (e.g., anatase-type titanium oxide particles, rutile-type titanium oxide particles, etc.), barium sulfate, zinc oxide, calcium carbonate, etc. Among them, titanium oxide is preferred as a white pigment.
[0275] In addition, a bright pigment may be included as a colorant. Examples of bright pigments include pearl pigment powder, metal powder such as aluminum powder and stainless steel powder, metal flakes, glass beads, glass flakes, mica, flaky iron oxide (MIO), and the like.
[0276] The coloring agent may be used alone or in combination of two or more.
[0277] The colorant may be a colorant that has been subjected to a surface treatment as required, or may be used in combination with a dispersant. In addition, two or more colorants may be used in combination.
[0278] The content of the colorant is, for example, preferably from 1 mass % to 30 mass % both inclusive, and more preferably from 3 mass % to 15 mass % both inclusive, based on the entire toner particles.
[0279] -Release agent-
[0280] Examples of the release agent include hydrocarbon waxes, natural waxes such as carnauba wax, rice wax, and candelilla wax, synthetic waxes such as montan wax, or mineral and petroleum waxes, and ester waxes such as fatty acid esters and montanic acid esters. The release agent is not limited thereto.
[0281] The melting temperature of the release agent is preferably 50°C to 110°C, more preferably 60°C to 100°C.
[0282] The melting temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC) by the “melting peak temperature” described in the method for measuring melting temperature in JIS K 7121-1987 “Method for measuring transition temperatures of plastics”.
[0283] The content of the release agent is, for example, preferably from 1 mass % to 20 mass % both inclusive, and more preferably from 5 mass % to 15 mass % both inclusive, based on the entire toner particles.
[0284] -Other additives-
[0285] Examples of other additives include known additives such as magnetic materials, charge control agents, and inorganic powders. These additives may be contained in the toner particles as internal additives.
[0286] -Characteristics of toner particles, etc.-
[0287] The toner particles may be toner particles of a single-layer structure, or may be toner particles of a so-called core / shell structure composed of a core portion (core particle) and a coating layer (shell layer) that covers the core portion.
[0288] Here, the toner particles of the core / shell structure may be composed of, for example, a core portion including a binder resin and, if necessary, other additives such as a colorant and a release agent, and a coating layer including a binder resin.
[0289] The volume average particle diameter (D50v) of the toner particles is preferably from 2 μm to 10 μm, and more preferably from 4 μm to 8 μm.
[0290] Incidentally, various average particle diameters and various particle size distribution indices of the toner particles were measured using Coulter Multisizer II (manufactured by Beckman Coulter) and an electrolyte using ISOTON-II (manufactured by Beckman Coulter).
[0291] In the measurement, 0.5 mg to 50 mg of the measurement sample is added to 2 ml of a 5 mass % aqueous solution of a surfactant (preferably sodium alkylbenzene sulfonate) as a dispersant, and the solution is added to 100 ml to 150 ml of the electrolyte.
[0292] The electrolyte in which the sample was suspended was dispersed by an ultrasonic disperser for 1 minute, and the particle size distribution of particles with a particle size ranging from 2 μm to 60 μm was measured by Coulter Multisizer II using an aperture of 100 μm. The number of particles sampled was 50,000.
[0293] Relative to the particle size range (segments) divided based on the measured particle size distribution, the volume and number are plotted as cumulative distributions starting from the smaller diameter side, the particle size at the cumulative 16% point is defined as the volume particle size D16v and the number particle size D16p, the particle size at the cumulative 50% point is defined as the volume average particle size D50v and the cumulative number average particle size D50p, and the particle size at the cumulative 84% point is defined as the volume particle size D84v and the number particle size D84p.
[0294] Using these values, the volume particle size distribution index (GSDv) is calculated as (D84v / D16v) 1 / 2 Calculate the particle size distribution index (GSDp) by (D84p / D16p) 1 / 2 Calculated.
[0295] The average circularity of the toner particles is preferably 0.94 or more and 1.00 or less, and more preferably 0.95 or more and 0.98 or less.
[0296] The average circularity of the toner particles is calculated by (equivalent circular circumference) / (circumference) [(circumference of a circle having the same projected area as the particle image) / (circumference of the particle projected image)]. Specifically, it is a value measured by the following method.
[0297] First, the toner particles to be measured are collected by suction and formed into a flat flow, and the particles are momentarily strobed to obtain a particle image as a still image, and the particle image is analyzed by a flow particle image analyzer (FPIA-3000 manufactured by Sysmex) to obtain the average circularity. The number of samples for obtaining the average circularity is set to 3500.
[0298] In addition, when the toner has an external additive, the toner (developer) to be measured is dispersed in water containing a surfactant, and then subjected to ultrasonic treatment to obtain toner particles from which the external additive is removed.
[0299] (External Additives)
[0300] Examples of the external additive include inorganic particles. Examples of the inorganic particles include SiO 2 、TiO 2 、Al 2 O 3 , CuO, ZnO, SnO 2 、CeO 2 , Fe 2 O 3 , MgO, BaO, CaO, K 2 O、Na 2 O、ZrO 2 、CaO·SiO 2, K 2 O·(TiO 2 )n、Al 2 O 3 ·2SiO 2 、CaCO 3 MgCO 3 ,BaSO 4 MgSO 4 wait.
[0301] The surface of the inorganic particles as an external additive is suitably subjected to hydrophobization. The hydrophobization is carried out by, for example, immersing the inorganic particles in a hydrophobization treatment agent. The hydrophobization treatment agent is not particularly limited, and for example, silane coupling agents, silicone oils, titanate coupling agents, aluminum coupling agents, etc. can be cited. They can be used alone or in combination of two or more.
[0302] The amount of the hydrophobizing agent is usually, for example, 1 part by mass or more and 10 parts by mass or less relative to 100 parts by mass of the inorganic particles.
[0303] Examples of the external additives include resin particles (polystyrene, polymethyl methacrylate (PMMA), melamine resin and other resin particles), detergent active agents (metal salts of higher fatty acids such as zinc stearate, and particles of fluorine-based high molecular weight bodies).
[0304] The amount of the external additive added is, for example, preferably 0.01% by mass or more and 5% by mass or less, and more preferably 0.01% by mass or more and 2.0% by mass or less, based on the toner particles.
[0305] (Method for producing toner)
[0306] Next, a method for producing a toner according to the present embodiment will be described.
[0307] The toner according to the present embodiment is obtained by manufacturing toner particles and then adding an external additive to the toner particles.
[0308] The toner particles can be produced by any of dry methods (such as kneading and pulverization methods) and wet methods (such as aggregation and aggregation methods, suspension polymerization methods, and dissolution suspension methods). The method for producing the toner particles is not particularly limited to these methods, and a known method can be used.
[0309] Among these, toner particles can be obtained by an aggregation and coalescence method (aggregation-based method).
[0310] Specifically, for example, in the case of manufacturing toner particles by an agglomeration and merging method, the toner particles are manufactured through the following steps: a step of preparing a resin particle dispersion in which resin particles serving as a binding resin are dispersed (resin particle dispersion preparation step); a step of agglomerating resin particles (and other particles if necessary) in the resin particle dispersion (in a dispersion after mixing other particle dispersions if necessary) to form agglomerated particles (agglomerated particle formation step); and a step of heating the agglomerated particle dispersion in which the agglomerated particles are dispersed to fuse / merge the agglomerated particles to form toner particles (fusion / merging step).
[0311] The details of each step are described below.
[0312] It should be noted that, in the following description, a method for obtaining toner particles containing a colorant and a release agent is described, but the colorant and the release agent are additives used as needed. Of course, other additives besides the colorant and the release agent may also be used.
[0313] - Resin particle dispersion preparation step -
[0314] First, a resin particle dispersion in which resin particles as a binder resin are dispersed is prepared, and at the same time, for example, a colorant particle dispersion in which colorant particles are dispersed and a release agent particle dispersion in which release agent particles are dispersed are prepared.
[0315] Here, the resin particle dispersion is prepared, for example, by dispersing the resin particles in a dispersion medium using a surfactant.
[0316] Examples of the dispersion medium used for the resin particle dispersion include aqueous media.
[0317] Examples of the aqueous medium include water such as distilled water and ion-exchanged water, alcohols, etc. These media may be used alone or in combination of two or more.
[0318] Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonates, phosphates, and soaps; cationic surfactants such as amine salts and quaternary ammonium salts; nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyols; and the like. Among these, anionic surfactants and cationic surfactants can be particularly mentioned. Nonionic surfactants can also be used in combination with anionic surfactants or cationic surfactants.
[0319] The surfactant may be used alone or in combination of two or more.
[0320] In the resin particle dispersion, as a method for dispersing the resin particles in the dispersion medium, for example, a common dispersion method using a rotary shearing homogenizer or a ball mill, sand mill, bead mill, etc. having a medium can be cited. In addition, depending on the type of the resin particles, the resin particles can also be dispersed in the resin particle dispersion by, for example, a phase inversion emulsification method.
[0321] It should be noted that the phase inversion emulsification method is the following method: the resin to be dispersed is dissolved in a hydrophobic organic solvent that can dissolve the resin, a base is added to the organic continuous phase (O phase) for neutralization, and then an aqueous medium (W phase) is added to perform discontinuity by converting the resin from W / O to O / W (the so-called phase inversion), so that the resin is dispersed in the aqueous medium in the form of particles.
[0322] The volume average particle size of the resin particles dispersed in the resin particle dispersion is, for example, preferably 0.01 μm or more and 1 μm or less, more preferably 0.08 μm or more and 0.8 μm or less, and further preferably 0.1 μm or more and 0.6 μm or less.
[0323] It should be noted that the volume average particle size of the resin particles is obtained by using a particle size distribution obtained by measurement using a laser diffraction particle size distribution measuring device (e.g., LA-700 manufactured by Horiba, Ltd.), and a cumulative distribution is plotted for the volume from the small particle size side relative to the divided particle size range (segment), and the particle size at which the accumulation of all particles reaches 50% is measured, which is taken as the volume average particle size D50v. It should be noted that the volume average particle size of particles in other dispersions is also measured in the same manner.
[0324] The content of the resin particles in the resin particle dispersion is, for example, preferably from 5 mass % to 50 mass %, and more preferably from 10 mass % to 40 mass %.
[0325] It should be noted that, for example, a colorant particle dispersion and a release agent particle dispersion are prepared in the same manner as the resin particle dispersion. That is, the volume average particle size of the particles in the resin particle dispersion, the dispersion medium, the dispersion method, and the content of the particles are the same for the colorant particles dispersed in the colorant particle dispersion and the release agent particles dispersed in the release agent particle dispersion.
[0326] It should be noted that in the case of manufacturing a colorant having the structure (1) above, in the resin particle dispersion preparation step, it is preferred to prepare a composite resin particle dispersion having a coating layer containing a binding resin (iii) (more preferably a vinyl resin B) around a core containing a binding resin (ii) (more preferably amorphous polyester resin A2).
[0327] For example, a resin particle dispersion of an amorphous polyester resin A2 having unsaturated double bonds is prepared, and a vinyl monomer and an initiator are added thereto for reaction, thereby producing a composite resin particle dispersion having a coating layer containing vinyl resin B around a core containing amorphous polyester resin A2.
[0328] In addition, it is preferred that a continuous phase resin particle dispersion containing a binder resin (i) (more preferably a resin particle dispersion containing amorphous polyester resin A1 and a resin particle dispersion containing crystalline polyester resin C) be prepared separately from the composite resin particle dispersion.
[0329] In the case of producing a toner having the structure of (2) above, it is preferred that the binder resin (II) contained in the discontinuous phase be a resin having a crosslinked structure. Specifically, it is preferred that a crosslinked structure (i.e., a gel structure) be formed in the binder resin (II) by a conventionally known method using a polymerization initiator, a crosslinking agent, etc. in at least one of the steps of preparing the resin particle dispersion or forming the aggregated particles.
[0330] - Agglomerated Particle Formation Step-
[0331] Next, the resin particle dispersion is mixed with the colorant particle dispersion and the release agent particle dispersion.
[0332] Then, the resin particles, the colorant particles, and the release agent particles are heterogeneously aggregated in the mixed dispersion to form aggregated particles containing the resin particles, the colorant particles, and the release agent particles and having a diameter close to that of the target toner particles.
[0333] It should be noted that, in the case of manufacturing a colorant having the structure described above (1), it is preferred to use the above-mentioned composite resin particle dispersion and a continuous phase resin particle dispersion containing a binding resin (i) as a resin particle dispersion to obtain a colorant having a structure having a continuous phase and a discontinuous phase (the discontinuous phase having a core and a coating layer).
[0334] Specifically, for example, a coagulant is added to the mixed dispersion, and the pH of the mixed dispersion is adjusted to acidity (for example, pH 2 to 5), a dispersion stabilizer is added as needed, and then heated to a temperature close to the glass transition temperature of the resin particles (specifically, for example, the glass transition temperature of the resin particles is -30°C to the glass transition temperature of -10°C), so that the particles dispersed in the mixed dispersion are agglomerated to form agglomerated particles.
[0335] In the aggregated particle forming step, for example, a coagulant may be added at room temperature (e.g., 25° C.) while the mixed dispersion is stirred using a rotary shearing homogenizer, the pH of the mixed dispersion is adjusted to acidic (e.g., pH 2 to 5), a dispersion stabilizer may be added as needed, and then the mixture may be heated.
[0336] Examples of the coagulant include: a surfactant having a polarity opposite to that of the surfactant used as a dispersant added to the mixed dispersion, an inorganic metal salt, and a metal complex having a valence of two or more. In particular, when a metal complex is used as the coagulant, the amount of the surfactant used is reduced and the charging characteristics are improved.
[0337] An additive that forms a complex or similar bond with the metal ion of the coagulant may be used as necessary. As the additive, a chelating agent is preferably used.
[0338] Examples of the inorganic metal salt include metal salts such as calcium chloride, calcium nitrate, barium chloride, magnesium chloride, zinc chloride, aluminum chloride, and aluminum sulfate; and inorganic metal salt polymers such as polyaluminum chloride, polyaluminum hydroxide, and calcium polysulfide.
[0339] As the chelating agent, a water-soluble chelating agent can be used. Examples of the chelating agent include hydroxycarboxylic acids such as tartaric acid, citric acid, and gluconic acid, iminodiacetic acid (IDA), nitrilotriacetic acid (NTA), and ethylenediaminetetraacetic acid (EDTA).
[0340] The amount of the chelating agent added is, for example, preferably 0.01 parts by mass or more and 5.0 parts by mass or less, and more preferably 0.1 parts by mass or more and less than 3.0 parts by mass, based on 100 parts by mass of the resin particles.
[0341] - Fusion / Merge Steps-
[0342] Next, the aggregated particle dispersion in which the aggregated particles are dispersed is heated to, for example, a temperature above the glass transition temperature of the resin particles (for example, a temperature 10 to 30° C. higher than the glass transition temperature of the resin particles) to fuse / merge (fuse and unify) the aggregated particles to form toner particles.
[0343] Through the above steps, toner particles are obtained.
[0344] It should be noted that after obtaining a dispersion of aggregated particles in which aggregated particles are dispersed, the toner particles can be manufactured through the following steps: further mixing the dispersion of aggregated particles with a dispersion of resin particles in which resin particles are dispersed, and aggregating the resin particles in a manner that further adheres to the surface of the aggregated particles to form second aggregated particles; and heating the second dispersion of aggregated particles in which the second aggregated particles are dispersed to fuse / merge the second aggregated particles to form toner particles with a core / shell structure.
[0345] Here, after the fusion / coalescing step is completed, the toner particles formed in the solution are subjected to a known washing step, a solid-liquid separation step, and a drying step to obtain dry toner particles.
[0346] Regarding the washing step, from the perspective of charging performance, replacement washing using ion exchange water can be fully implemented. In addition, the solid-liquid separation step is not particularly limited, and from the perspective of productivity, suction filtration, pressure filtration, etc. can be implemented. In addition, the method of the drying step is not particularly limited, and from the perspective of productivity, freeze drying, airflow drying, fluidized drying, vibration fluidized drying, etc. can be implemented.
[0347] Thereafter, for example, an external additive is added to the obtained dry toner particles and mixed, thereby producing the toner of the present embodiment. The mixing can be performed using, for example, a V-type blender, a Henschel mixer, a Loedige mixer, etc. Furthermore, coarse particles of the toner can be removed using a vibration sieving machine, a wind sieving machine, etc. as needed.
[0348] <Electrostatic Image Developer>
[0349] The electrostatic image developer according to the present embodiment includes at least the toner according to the present embodiment.
[0350] The electrostatic image developer of the present embodiment may be a one-component developer containing only the toner of the present embodiment, or may be a two-component developer in which the toner and a carrier are mixed.
[0351] The carrier is not particularly limited, and any known carrier may be used. Examples of the carrier include: a coated carrier in which a core material formed of magnetic powder is coated with a resin; a magnetic powder dispersed carrier in which magnetic powder is dispersed and mixed in a matrix resin; a resin impregnated carrier in which porous magnetic powder is impregnated with a resin; and the like.
[0352] Note that the magnetic powder dispersed carrier and the resin impregnated carrier may be carriers in which the constituent particles of the carrier are used as core materials and the core materials are coated with a coating resin.
[0353] Examples of the magnetic powder include magnetic metals such as iron, nickel, and cobalt; and magnetic oxides such as ferrite and magnetite.
[0354] Examples of the coating resin and the base resin include polyethylene, polypropylene, polystyrene, polyvinyl acetate, polyvinyl alcohol, polyvinyl butyral, polyvinyl chloride, polyvinyl ether, polyvinyl ketone, vinyl chloride-vinyl acetate copolymer, styrene-acrylate copolymer, a straight-chain silicone resin containing an organic siloxane bond or a modified product thereof, a fluororesin, a polyester, a polycarbonate, a phenol resin, an epoxy resin, and the like.
[0355] It should be noted that the coating resin and the base resin may contain other additives such as conductive particles.
[0356] Examples of the conductive particles include particles of metals such as gold, silver, and copper, carbon black, titanium oxide, zinc oxide, tin oxide, barium sulfate, aluminum borate, and potassium titanate.
[0357] Here, when utilizing the coating resin to coat the surface of the core material, a coating layer forming solution obtained by dissolving the coating resin and various additives as necessary in a suitable solvent can be cited as a coating method, etc. The solvent is not particularly limited and can be selected by considering the coating resin used, coating suitability, etc.
[0358] Specific resin coating methods include: an immersion method, in which the core material is immersed in a coating layer forming solution; a spray method, in which the coating layer forming solution is sprayed onto the surface of the core material; a fluidized bed method, in which the coating layer forming solution is sprayed while the core material is suspended by flowing air; a kneading coater method, in which the core material of the carrier is mixed with the coating layer forming solution in a kneading coater and then the solvent is removed; and the like.
[0359] The mixing ratio (mass ratio) of the toner and the carrier in the two-component developer is preferably toner:carrier=1:100 to 30:100, and more preferably 3:100 to 20:100.
[0360] <Image Forming Apparatus / Image Forming Method>
[0361] The image forming apparatus and image forming method according to the present embodiment will be described.
[0362] The image forming device of the present embodiment comprises: an image holder; a charging mechanism for charging the surface of the image holder; an electrostatic image forming mechanism for forming an electrostatic image on the surface of the charged image holder; a developing mechanism for storing an electrostatic image developer and developing the electrostatic image formed on the surface of the image holder into a toner image using the electrostatic image developer; a transfer mechanism for transferring the toner image formed on the surface of the image holder to the surface of a recording medium; and a fixing mechanism for fixing the toner image transferred to the surface of the recording medium. In addition, as the electrostatic image developer, the electrostatic image developer of the present embodiment is applied.
[0363] The image forming device of the present embodiment is implemented by the following image forming method (the image forming method of the present embodiment), and the image forming method has the following steps: a charging step, charging the surface of the image retaining body; an electrostatic image forming step, forming an electrostatic image on the surface of the charged image retaining body; a developing step, developing the electrostatic image formed on the surface of the image retaining body into a toner image using the electrostatic image developer of the present embodiment; a transfer step, transferring the toner image formed on the surface of the image retaining body to the surface of the recording medium; and a fixing step, fixing the toner image transferred to the surface of the recording medium.
[0364] The image forming device of this embodiment is suitable for the following well-known image forming devices: a device using a direct transfer method for directly transferring a toner image formed on the surface of an image holder to a recording medium; a device using an intermediate transfer method for transferring a toner image formed on the surface of an image holder to the surface of an intermediate transfer body for the first time, and transferring the toner image transferred to the surface of the intermediate transfer body to the surface of a recording medium for a second time; a device having a cleaning mechanism for cleaning the surface of the image holder after the toner image is transferred and before charging; a device having a de-staticizing mechanism for de-staticizing the surface of the image holder by irradiating de-staticizing light to the surface of the image holder after the toner image is transferred and before charging; and the like.
[0365] In the case of an intermediate transfer type device, the transfer mechanism is, for example, composed of the following components: an intermediate transfer body to the surface of which the toner image is transferred; a primary transfer mechanism that transfers the toner image formed on the surface of the image retaining body to the surface of the intermediate transfer body for the first time; and a secondary transfer mechanism that transfers the toner image transferred to the surface of the intermediate transfer body to the surface of the recording medium for the second time.
[0366] It should be noted that, in the image forming apparatus of the present embodiment, the portion including the developing mechanism may be a cartridge structure (processing box) that is loaded and unloaded in the image forming apparatus. As the processing box, for example, a processing box that stores the electrostatic image developer of the present embodiment and has a developing mechanism is suitable for use.
[0367] An example of the image forming apparatus according to the present embodiment is shown below, but the present invention is not limited thereto. It should be noted that the main parts shown in the drawings will be described, and the description of other parts will be omitted.
[0368] Figure 2 2 is a diagram schematically showing the structure of the image forming apparatus according to the present embodiment.
[0369] Figure 2The image forming apparatus shown in the figure has first to fourth image forming units 10Y, 10M, 10C, 10K (image forming mechanism) of an electronic photographic method for outputting images of yellow (Y), magenta (M), cyan (C), and black (K) based on color separation image data. These image forming units (hereinafter sometimes referred to as "units") 10Y, 10M, 10C, 10K are arranged in parallel with each other at a predetermined distance in the horizontal direction. It should be noted that these units 10Y, 10M, 10C, 10K may be process cartridges that are loaded and unloaded in the image forming apparatus.
[0370] In the upper part of each unit 10Y, 10M, 10C, 10K in the drawing, an intermediate transfer belt 20 as an intermediate transfer body is extended through each unit. The intermediate transfer belt 20 is wound around a driving roller 22 and a support roller 24 that are arranged separately from each other in the direction from left to right in the drawing, so that it runs in the direction from the first unit 10Y to the fourth unit 10K. It should be noted that the support roller 24 is applied with a force in a direction away from the driving roller 22 by a spring or the like that is not shown in the figure, and tension is applied to the intermediate transfer belt 20 wound around the two. In addition, an intermediate transfer body cleaning device 30 is provided on the image holding body side of the intermediate transfer belt 20, which is opposite to the driving roller 22.
[0371] In addition, toner including four colors of yellow, magenta, cyan and black stored in toner boxes 8Y, 8M, 8C and 8K are supplied to the developing devices (developing mechanisms) 4Y, 4M, 4C and 4K of the respective units 10Y, 10M, 10C and 10K.
[0372] Since the first to fourth units 10Y, 10M, 10C, and 10K have the same configuration, the first unit 10Y disposed on the upstream side in the running direction of the intermediate transfer belt for forming a yellow image will be described as a representative. It should be noted that the parts identical to the first unit 10Y are marked with reference numerals with magenta (M), cyan (C), and black (K) instead of yellow (Y), and the description of the second to fourth units 10M, 10C, and 10K will be omitted.
[0373] The first unit 10Y has a photoreceptor 1Y that functions as an image holder. The following are arranged in order around the photoreceptor 1Y: a charging roller (an example of a charging mechanism) 2Y that charges the surface of the photoreceptor 1Y to a preset potential; an exposure device (an example of an electrostatic image forming mechanism) 3 that forms an electrostatic image by exposing the charged surface using a laser beam 3Y based on a color separation image signal; a developing device (an example of a developing mechanism) 4Y that supplies the charged toner to the electrostatic image to develop the electrostatic image; a primary transfer roller 5Y (an example of a primary transfer mechanism) that transfers the developed toner image to the intermediate transfer belt 20; and a photoreceptor cleaning device (an example of a cleaning unit) 6Y that removes the toner remaining on the surface of the photoreceptor 1Y after the primary transfer.
[0374] It should be noted that the primary transfer roller 5Y is arranged inside the intermediate transfer belt 20 and is disposed at a position opposite to the photoreceptor 1Y. Furthermore, each of the primary transfer rollers 5Y, 5M, 5C, and 5K is connected to a bias power supply (not shown) for applying a primary transfer bias. Each bias power supply changes the value of the transfer bias applied to each primary transfer roller by control of a control unit (not shown).
[0375] Next, the operation of forming a yellow image in the first unit 10Y will be described.
[0376] First, before the operation, the surface of the photoreceptor 1Y is charged to a potential of -600 V to -800 V by the charging roller 2Y.
[0377] The photoreceptor 1Y has a conductivity (e.g., a volume resistivity of 1×10 -6 The photosensitive layer is formed by laminating a photosensitive layer on a substrate with a resistance of 100 Ωcm or less. The photosensitive layer generally has a high resistance (resistance of a common resin), but has a property that the resistivity of the portion irradiated with the laser beam changes when the laser beam 3Y is irradiated. Therefore, the laser beam 3Y is output to the charged surface of the photoreceptor 1Y by the exposure device 3 according to the image data for yellow sent from the control unit not shown. The laser beam 3Y is irradiated to the photosensitive layer on the surface of the photoreceptor 1Y, thereby forming an electrostatic image of a yellow image pattern on the surface of the photoreceptor 1Y.
[0378] The electrostatic image is an image formed on the surface of the photoreceptor 1Y by charging, which is a so-called negative latent image. The negative latent image is formed as follows: the resistivity of the irradiated portion of the photosensitive layer is reduced by using the laser beam 3Y, so that the charged charge on the surface of the photoreceptor 1Y flows; on the other hand, the charge of the portion not irradiated with the laser beam 3Y remains, thereby forming the negative latent image.
[0379] The electrostatic image formed on the photoreceptor 1Y rotates to a preset development position as the photoreceptor 1Y moves. At the development position, the electrostatic image on the photoreceptor 1Y is visualized (developed) by the developing device 4Y to form a toner image.
[0380] The developing device 4Y stores an electrostatic image developer containing, for example, at least a yellow toner and a carrier. The yellow toner is frictionally charged by stirring inside the developing device 4Y, and is held on a developer roller (an example of a developer holding member) by a charge having the same polarity (negative polarity) as the charge charged on the photoreceptor 1Y. After that, the surface of the photoreceptor 1Y passes through the developing device 4Y, whereby the yellow toner is electrostatically attached to the latent image portion on the surface of the photoreceptor 1Y that has been de-charged, and the latent image is developed using the yellow toner. The photoreceptor 1Y formed with the yellow toner image continues to run at a preset speed, and the toner image developed on the photoreceptor 1Y is conveyed to a preset primary transfer position.
[0381] When the yellow toner image on the photoreceptor 1Y is transferred to the primary transfer roller 5Y, a primary transfer bias is applied to the primary transfer roller 5Y, and the electrostatic force from the photoreceptor 1Y toward the primary transfer roller 5Y acts on the toner image, and the toner image on the photoreceptor 1Y is transferred to the intermediate transfer belt 20. The transfer bias applied at this time has a polarity (+) opposite to the polarity (-) of the toner, and is controlled to, for example, +10 μA by a control unit (not shown) in the first unit 10Y.
[0382] On the other hand, the toner remaining on the photoreceptor 1Y is removed and recovered by the photoreceptor cleaning device 6Y.
[0383] In addition, the primary transfer bias applied to the primary transfer rollers 5M, 5C, and 5K after the second unit 10M is also controlled in accordance with the first unit.
[0384] In this way, the intermediate transfer belt 20 to which the yellow toner image has been transferred by the first unit 10Y is transported sequentially through the second to fourth units 10M, 10C, and 10K, so that the toner images of the respective colors are multi-transferred in a superimposed manner.
[0385] The intermediate transfer belt 20 to which the four-color toner image has been multi-transferred by the first to fourth units arrives at the secondary transfer section, which is composed of the intermediate transfer belt 20, the support roller 24 in contact with the inner surface of the intermediate transfer belt, and the secondary transfer roller (an example of the secondary transfer mechanism) 26 arranged on the image holding surface side of the intermediate transfer belt 20. On the other hand, the recording paper (an example of the recording medium) P is fed to the gap between the secondary transfer roller 26 and the intermediate transfer belt 20 at a preset timing by the feeding member, and a secondary transfer bias is applied to the support roller 24. The transfer bias applied at this time has the same (-) polarity as the polarity (-) of the toner, and the electrostatic force from the intermediate transfer belt 20 to the recording paper P acts on the toner image, so that the toner image on the intermediate transfer belt 20 is transferred to the recording paper P. It should be noted that the secondary transfer bias at this time is determined based on the resistance detected by the resistance detection mechanism (not shown) that detects the resistance of the secondary transfer section, and the voltage is controlled.
[0386] Thereafter, the recording paper P is fed into a pressure-contact portion (nip portion) of a pair of fixing rollers in a fixing device (an example of a fixing mechanism) 28 , and the toner image is fixed on the recording paper P to form a fixed image.
[0387] Examples of the recording paper P to which the toner image is transferred include plain paper used in electrophotographic copy machines, printers, etc. Examples of the recording medium include, in addition to the recording paper P, OHP transparent films, etc.
[0388] In order to further improve the smoothness of the image surface after fixing, the surface of the recording paper P is preferably smooth. For example, coated paper obtained by coating the surface of ordinary paper with a resin or the like, art paper for printing, etc. are preferably used.
[0389] The recording paper P on which the color image has been fixed is sent out to the discharge portion, and a series of color image forming operations are completed.
[0390] <Process Cartridge / Toner Cartridge>
[0391] The process cartridge according to this embodiment will be described.
[0392] The process cartridge of this embodiment is a process cartridge that is detachably mounted in an image forming apparatus and includes a developing mechanism that stores the electrostatic image developer of this embodiment and develops the electrostatic image formed on the surface of the image holding member into a toner image using the electrostatic image developer.
[0393] It should be noted that the process cartridge of this embodiment is not limited to the above-mentioned structure, but may also be provided with a developing device and, if necessary, at least one of other mechanisms selected from an image holder, a charging mechanism, an electrostatic image forming mechanism, and a transfer mechanism.
[0394] An example of the process cartridge according to the present embodiment is shown below, but the present invention is not limited thereto. It should be noted that the main parts shown in the drawings will be described, and the description of other parts will be omitted.
[0395] Figure 3 1 is a schematic diagram showing the structure of the process cartridge according to the present embodiment.
[0396] Figure 3 The processing box 200 shown is constructed by, for example, using a shell 117 having a mounting guide 116 and an opening 118 for exposure to integrally combine and hold a photosensitive body 107 (an example of an image holding body) and a charging roller 108 (an example of a charging mechanism) provided around the photosensitive body 107, a developing device 111 (an example of a developing mechanism), and a photosensitive body cleaning device 113 (an example of a cleaning unit) to form an ink cartridge.
[0397] It should be noted that Figure 3 109 denotes an exposure device (an example of an electrostatic image forming mechanism), 112 denotes a transfer device (an example of a transfer mechanism), 115 denotes a fixing device (an example of a fixing mechanism), and 300 denotes recording paper (an example of a recording medium).
[0398] Next, the toner cartridge according to the present embodiment will be described.
[0399] The toner cartridge of the present embodiment stores the toner of the present embodiment and is attached to and detached from an image forming apparatus. The toner cartridge stores replenishment toner to be supplied to a developing mechanism provided in the image forming apparatus.
[0400] It should be noted that Figure 2 The image forming apparatus shown is an image forming apparatus having a structure of attaching and detaching toner cartridges 8Y, 8M, 8C, and 8K, and the developing devices 4Y, 4M, 4C, and 4K are connected to the toner cartridges corresponding to the respective developing devices (colors) by toner supply pipes not shown. In addition, when the toner stored in the toner cartridge is insufficient, the toner cartridge is replaced.
[0401] Example
[0402] The present invention is described in more detail below by way of examples, but the present invention is not limited to the following examples unless it exceeds the gist thereof. It should be noted that, hereinafter, "parts" and "%" are by mass unless otherwise stated.
[0403] [Example (1)]
[0404] <Synthesis of Crystalline Polyester Resin 1>
[0405] 225 parts of 1,10-dodecanedioic acid, 174 parts of 1,10-decanediol and 0.8 parts of dibutyltin oxide as a catalyst were added to a three-necked flask that was heated and dried. The air in the three-necked flask was then replaced with nitrogen by a reduced pressure operation to form an inert atmosphere. The mixture was stirred at 180°C for 5 hours and refluxed by mechanical stirring to allow the reaction to proceed. The water generated in the reaction system was distilled off during the reaction. The mixture was then slowly heated to 230°C and stirred for 2 hours under reduced pressure. After the mixture became viscous, the molecular weight was confirmed by GPC. When the weight average molecular weight reached 17,500, the reduced pressure distillation was stopped to obtain a crystalline polyester resin 1.
[0406] <Synthesis of Amorphous Polyester Resin 1>
[0407] Bisphenol A propylene oxide adduct: 367 parts
[0408] Bisphenol A ethylene oxide adduct: 230 parts
[0409] Terephthalic acid: 163 parts
[0410] ·Trimellitic anhydride: 20 parts
[0411] Dibutyltin oxide: 4 parts
[0412] After the above components were placed in a three-necked flask that was heated and dried, the air in the container was decompressed by a decompression operation, and nitrogen was further used to make an inert atmosphere, and the reaction was carried out at 230°C and normal pressure (101.3 kPa) for 10 hours with mechanical stirring, and further at 8 kPa for 1 hour. After cooling to 210°C, 4 parts of trimellitic anhydride were added, and the reaction was carried out for 1 hour, and then the reaction was carried out at 8 kPa until the softening temperature reached 118°C, to obtain amorphous polyester resin 1.
[0413] It should be noted that regarding the softening temperature of the resin, a flow tester (Shimadzu Corporation, CFT-5000) was used to heat 1 g of the sample at a heating rate of 6°C / min. A load of 1.96 MPa was applied using a plunger, and the sample was extruded from a nozzle with a diameter of 1 mm and a length of 1 mm. The temperature at which half of the sample flowed out was taken as the softening temperature of the resin.
[0414] <Synthesis of Amorphous Polyester Resin 2>
[0415] Bisphenol A propylene oxide adduct: 469 parts
[0416] Bisphenol A ethylene oxide adduct: 137 parts
[0417] Terephthalic acid: 152 parts
[0418] Fumaric acid: 20 parts
[0419] Dibutyltin oxide: 4 parts
[0420] After adding the above components to a three-necked flask that was heated and dried, the air in the container was decompressed by a decompression operation, and further inert atmosphere was formed by nitrogen, and the reaction was carried out at 230°C and normal pressure (101.3 kPa) with mechanical stirring for 10 hours, and further at 8 kPa for 1 hour. After cooling to 210°C, 4 parts of trimellitic anhydride were added, and the reaction was carried out for 1 hour, and then the reaction was carried out at 8 kPa until the softening temperature reached 107°C, to obtain amorphous polyester resin 2.
[0421] <Preparation of Crystalline Polyester Resin Particle Dispersion Liquid 1>
[0422] Crystalline resin 1 (100 parts), 40 parts of methyl ethyl ketone and 30 parts of isopropyl alcohol were placed in a separable flask, fully mixed and dissolved at 75°C, and then 6.0 parts of 10% ammonia solution were added dropwise. The heating temperature was lowered to 60°C, and ion exchange water was added dropwise at a liquid delivery rate of 6 g / min using a liquid delivery pump under stirring. After the liquid became uniformly turbid, the liquid delivery rate was increased to 25 g / min. After the total liquid volume reached 400 parts, the addition of ion exchange water was stopped. The solvent was then removed under reduced pressure to obtain a crystalline polyester resin dispersion 1. The obtained crystalline polyester resin particle dispersion 1 had a volume average particle size of 168 nm and a solid content concentration of 11.5%.
[0423] <Preparation of Amorphous Polyester Resin Particle Dispersion Liquid 1>
[0424] ·Amorphous polyester resin 1: 300 parts
[0425] Methyl ethyl ketone: 218 parts
[0426] Isopropyl alcohol: 60 parts
[0427] 10% ammonia solution: 10.6 parts
[0428] The above components (after removing the insoluble components for the amorphous polyester resin) were placed in a separable flask, mixed and dissolved, and then ion exchange water was added dropwise at a liquid delivery rate of 8 g / min using a liquid delivery pump while heating and stirring at 40°C. After the liquid became turbid, the liquid delivery rate was increased to 12 g / min to make it phase inverted, and the dropwise addition was stopped after the liquid delivery amount reached 1050 parts. Thereafter, the solvent was removed under reduced pressure to obtain amorphous polyester resin particle dispersion 1. The volume average particle size of the amorphous polyester resin particle dispersion 1 was 168 nm, and the solid content concentration was 30%.
[0429] <Preparation of Amorphous Polyester Resin Particle Dispersion Liquid 2>
[0430] ·Amorphous polyester resin 2: 300 parts
[0431] Methyl ethyl ketone: 150 parts
[0432] Isopropyl alcohol: 50 parts
[0433] 10% ammonia solution: 10.6 parts
[0434] The above components (after removing the insoluble components for the amorphous polyester resin) were placed in a separable flask, mixed and dissolved, and then ion exchange water was added dropwise at a liquid delivery rate of 8 g / min using a liquid delivery pump while heating and stirring at 40°C. After the liquid became turbid, the liquid delivery rate was increased to 12 g / min to make it phase inverted, and the dropwise addition was stopped after the liquid delivery amount reached 1050 parts. Thereafter, the solvent was removed under reduced pressure to obtain amorphous polyester resin dispersion 2. The volume average particle size of the amorphous polyester resin particle dispersion 2 was 170 nm, and the solid content concentration was 30%.
[0435] <Vinyl / amorphous polyester composite resin particle dispersion 1>
[0436] ·Amorphous polyester resin particle dispersion 2: 160 parts
[0437] Butyl acrylate: 192 parts
[0438] 10% ammonia solution: 3.6 parts
[0439] The above components and 253 parts of ion exchange water were placed in a 2L cylindrical stainless steel container, and the homogenizer (manufactured by IKA, ULTRA-TURRAXT50) was rotated at 10000 rpm for 10 minutes for dispersion and mixing. The raw material dispersion was then transferred to a polymerization kettle equipped with a stirring device using a stirring blade with two impellers and a thermometer, and the stirring speed was set to 200 rpm under a nitrogen atmosphere. Heating was started using a heating jacket and maintained at 75°C for 30 minutes. After that, a mixed solution of 1.8 parts of potassium persulfate and 120 parts of ion exchange water was added dropwise using a liquid delivery pump for 120 minutes, and then maintained at 75°C for 210 minutes. After the liquid temperature was lowered to 50°C, 5.4 parts of anionic surfactant (manufactured by Dow Chemical, Dowfax 2A1) were added to obtain a vinyl / amorphous polyester composite resin particle dispersion 1 as a particle dispersion of vinyl / amorphous polyester composite resin 1. The obtained vinyl / amorphous polyester composite resin particle dispersion 1 had a volume average particle size of 220 nm and a solid content concentration of 32%.
[0440] In the vinyl / amorphous polyester composite resin particle dispersion 1, the glass transition temperature Tg of the vinyl resin constituting the coating layer is lower than the temperature (150° C.) of the fixing device in the <Evaluation / Image Roughness> described later.
[0441] <Preparation of Release Agent Dispersion>
[0442] Solid paraffin HNP9 (manufactured by Nippon Seira Co., Ltd.): 500 parts
[0443] Anionic surfactant (Dowfax 2A1 manufactured by Dow Chemical): 50 parts
[0444] Ion exchange water: 1700 parts
[0445] The above components were heated to 110° C., dispersed using a homogenizer (ULTRA-TURRAXT50 manufactured by IKA), and then dispersed using a Manton Gaulin high pressure homogenizer (Gaulin) to prepare a release agent dispersion 1 (solid content concentration: 32%) in which a release agent having an average particle size of 180 nm was dispersed.
[0446] <Preparation of Cyan Pigment Dispersion>
[0447] Pigment Blue 15:3 (DIC): 200 copies
[0448] Anionic surfactant (Dowfax 2A1 manufactured by Dow Chemical): 1.5 parts
[0449] Ion exchange water: 800 parts
[0450] The above components were mixed and dispersed for about 1 hour using a disperser Cavitron (CR1010 manufactured by Pacific Machinery Co., Ltd.) to prepare a cyan pigment dispersion (solid content concentration: 20%).
[0451] <Production of Cyan Toner 1>
[0452] Amorphous polyester resin particle dispersion 1: (amount described in Table 2)
[0453] · Vinyl / amorphous polyester composite resin particle dispersion 1: (amount described in Table 2)
[0454] Crystalline polyester resin particle dispersion 1: (amount described in Table 2)
[0455] Release agent dispersion 1: 45 parts
[0456] Cyan pigment dispersion: 90 parts
[0457] Anionic surfactant (Dow Chemical Co., Ltd., Dowfax 2A1): 1.40 parts
[0458] The above raw materials were placed in a 2L cylindrical stainless steel container and dispersed and mixed for 10 minutes using a homogenizer (ULTRA-TURRAXT50 manufactured by IKA) at 4000 rpm while applying shear force. Then, 1.75 parts of a 10% nitric acid aqueous solution of polyaluminum chloride as a coagulant was slowly added dropwise, and the homogenizer was rotated at 5000 rpm for 15 minutes to disperse and mix, thereby preparing a raw material dispersion.
[0459] Thereafter, the raw material dispersion was transferred to a polymerization reactor equipped with a stirring device using two impellers and a thermometer, and the stirring speed was set to 550 rpm and heating was started using a heating jacket to promote the growth of aggregated particles at 49° C. In addition, at this time, the pH of the raw material dispersion was controlled in the range of 2.2 to 3.5 using 0.3 M nitric acid and 1 M sodium hydroxide aqueous solution. The above pH range was maintained for about 2 hours to form aggregated particles.
[0460] Next, add amorphous polyester resin particle dispersion 1 (184 parts) to attach the resin particles of the adhesive resin to the surface of the above-mentioned agglomerated particles. Further heat to 53°C, prepare agglomerated particles, and confirm the size and morphology of the particles using an optical microscope and MultisizerII. Thereafter, adjust the pH to 7.8 using a 5% sodium hydroxide aqueous solution and maintain for 15 minutes. Thereafter, in order to fuse the agglomerated particles, raise the pH to 8.0 and then raise the temperature to 85°C. After confirming the fusion of the agglomerated particles using an optical microscope, stop heating after 2 hours and cool at a cooling rate of 1.0°C / minute. Thereafter, sieve with a 20μm mesh, repeatedly wash with water, and dry with a vacuum dryer to obtain cyan toner particles 1.
[0461] 0.5% of silica (average particle size 40 nm) treated with hexamethyldisilazane and 0.7% of a titanium compound (average particle size 30 nm) obtained by treating metatitanic acid with 50% isobutyltrimethoxysilane and then calcining were added as external additives to the obtained cyan toner particles 1, and mixed for 10 minutes using a 75L Henschel mixer, and then sieved using a wind sieving machine HI-BOLTA 300 (manufactured by Shin Tokyo Machinery Co., Ltd.) to prepare cyan toner 1. The volume average particle size of the obtained cyan toner 1 was 5.8 μm.
[0462] The obtained amorphous polyester resins 1 and 2 and vinyl / amorphous polyester composite resin 1 were measured for "storage modulus G' at 50°C", "storage modulus G' at 100°C", and "tan δ in the entire temperature range of 50°C to 100°C" by the above-mentioned methods. In addition, for the vinyl / amorphous polyester composite resin 1, "storage modulus G' in the entire temperature range of 50°C to 100°C" and "content of tetrahydrofuran-insoluble components" were also measured. The results are shown in Table 1.
[0463] In addition, the “presence or absence of a continuous phase and a discontinuous phase having a core and a coating layer,” “the average equivalent circle diameter L1 [nm] of the discontinuous phase,” and “the average thickness L2 [nm] of the coating layer” of the obtained cyan toner particles 1 were confirmed or measured by the above-mentioned methods. The results are shown in Table 3.
[0464] Furthermore, the storage modulus G′ at 50° C. of the obtained cyan toner 1 was measured by the above method. 50T "Storage modulus G' at 100℃ 100T "tanδ in the entire temperature range of 50℃ to 100℃ T " ". In addition, for the contents other than the vinyl / amorphous polyester composite resin 1, the "storage modulus G' at 50°C" was measured by the above method. 50r "Storage modulus G' at 100℃ 100r The results are shown in Table 3.
[0465] <Preparation of Cyan Developer 1>
[0466] Next, 0.15 parts of vinylidene fluoride and 1.35 parts of a copolymer of methyl methacrylate and trifluoroethylene (polymerization ratio 80:20) were applied to 100 parts of a ferrite core having an average particle size of 35 μm using a kneader device to prepare a carrier. The obtained carrier and cyan toner 1 were mixed in a 2-liter V-type blender at a ratio of 100 parts:8 parts, respectively, to prepare cyan developer 1.
[0467] <Production of Cyan Toners 2 to 11 and B1 to B2, and Developers 2 to 11 and B1 to B2>
[0468] Cyan toners 2 to 11 and B1 to B2, and cyan developers 2 to 11 and B1 to B2 were prepared in the same manner as the cyan toner 1 and the cyan developer 1, except that the type and addition amount of each dispersion liquid used were changed as described in Table 2.
[0469] [Table 1]
[0470]
[0471] [Table 2]
[0472]
[0473]
[0474] <Evaluation / Image Rough>
[0475] In an image forming apparatus (manufactured by Fuji Xerox Corporation, product name: DocuPrint C2450 II), a pair of paper conveying rollers provided at both ends of the paper (both ends in a direction perpendicular to the paper conveying direction) immediately in front of the upstream side of the fixing member in the paper conveying direction were adjusted so as to produce a difference in rotational speed. Specifically, the rotational speed of one paper conveying roller was set to 70.2 m / s, and the rotational speed of the other paper conveying roller was set to 69.8 m / s.
[0476] The cyan developer shown in Table 3 was charged into the image forming apparatus, and an evaluation chart was formed so that the toner loading amount reached 10.0 g / cm 2 100 images were printed continuously at 25°C and 90% humidity. The image roughness of the 100th image was evaluated using the following evaluation criteria. The image area on the paper was 30%, the temperature of the fuser was 150°C, and the paper used was SP paper A3 with a basis weight of 60 g / m 2 (Made by Fuji Xerox Corporation).
[0477] A (◎): No image roughness occurs
[0478] B (○): The image is difficult to visually judge as rough
[0479] C(△): The image is slightly rough and within the allowable range
[0480] D(×): The image is clearly rough and is outside the tolerance range.
Claims
1. A toner for electrostatic image development, wherein: The toner contains at least a binder resin. The toner comprises a continuous phase and a discontinuous phase, the continuous phase comprising a binding resin i, the discontinuous phase comprising a core comprising a binding resin ii and a coating layer covering the core and comprising a binding resin iii, the continuous phase comprising a crystalline polyester resin a and a non-crystalline polyester resin b1 as the binding resin i, the core comprising a non-crystalline polyester resin b2 as the binding resin ii, and the coating layer comprising a vinyl resin c as the binding resin iii, The storage modulus G' of the toner at 50°C in the dynamic viscoelasticity measurement is 50T 2×10 6 Pa above 3×10 8 Pa below, storage modulus G' at 100℃ 100T 1×10 4 Pa or above 1×10 6 Below Pa, The tanδ of the toner in the entire temperature range of 50°C to 100°C is T It is greater than 0.05 and less than 1.
5.
2. The electrostatic image developing toner according to claim 1, wherein The above-mentioned adhesive resin includes at least: Crystalline resin A; Amorphous resin B1; and Amorphous resin B2, wherein the tan δ of the amorphous resin B2 in the entire temperature range of 50° C. to 100° C. in dynamic viscoelasticity measurement is B2 Less than 1, storage modulus G' in the entire temperature range of 50°C to 100°C 50-100B2 1×10 3 Pa or above 1×10 7 Pa or less, and the content of the tetrahydrofuran-insoluble component is 90 mass % or more and 100 mass % or less.
3. The electrostatic image developing toner according to claim 2, wherein The storage modulus G′ of the substance contained in the electrostatic image developing toner other than the amorphous resin B2 at 50° C. in the dynamic viscoelasticity measurement is 50R 3×10 6 Pa above 9×10 8 Pa or less, and the storage modulus G' at 100°C 100R 1×10 3 Pa or above 1×10 5 Below Pa.
4. The electrostatic image developing toner according to claim 2 or claim 3, wherein The crystalline resin A is a crystalline polyester resin. The amorphous resin B1 is an amorphous polyester resin. 5 . An electrostatic image developer, comprising the electrostatic image developing toner according to claim 1 . 6 . A toner cartridge that is detachably mounted in an image forming apparatus, the toner cartridge storing the electrostatic image developing toner according to claim 1 .
Citation Information
Patent Citations
Toner for developing electrostatic charge image
JP2002182427A
Toner, image forming method, and image forming apparatus
JP2004151438A
Toner, developer, image forming apparatus, and process cartridge
JP2015114364A
Toner, toner storage unit, and image forming apparatus
JP2017146568A
Binder resin composition for toner
JP2015072378A